Flash joule heating for preparing 1D carbon and / or boron nitride nanomaterials

Through the method of heating of flashing ear, it solves the problem of low productivity and resource consumption of one -dimensional carbon and boron nanoma materials in existing technologies, and achieves efficient and sustainable nanomaterial preparation.

CN119384867APending Publication Date: 2025-01-28WILLIAM MARCH RICE UNIVERSITY
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202380047293.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-05-13
Filing Date
2023-05-15
Publication Date
2025-01-28

AI Technical Summary

Technical Problem

The prior art has problems such as low productivity, high resource consumption, and the need for a large amount of metal catalysts when preparing one-dimensional carbon and boron nitride nanomaterials, and it is difficult to effectively utilize waste plastics.

Method used

Using flashing scorch ear heating (FJH) method, a mixture of the material and catalyst is applied to the voltage, and a one-dimensional structure is driven by driving the current, including graphite 1D and hybrid materials, boron nanomoltic tubes, chaos boron-carbon-nitrogen and mixing Miscellane.

Benefits of technology

The efficient and sustainable preparation of one -dimensional carbon and boron nanomide materials is achieved, improved productivity, reduced resource consumption, and avoided the use of a large number of metal catalysts.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119384867A_ABST
    Figure CN119384867A_ABST
Patent Text Reader

Abstract

Flash Joule Heating (FJH) for the preparation of one-dimensional (1D) carbon and / or boron nitride nanomaterials and 1D materials bonded to 0D, 1D, 2D and 3D nanomaterials, composites, nanostructures, networks, and mixtures thereof. Such materials produced by FJH include 1D carbon and hybrid nanomaterials, boron nitride nanotubes (BNNTs), disordered boron-carbon-nitrogen (BCN), doped (substituted) graphene, and heteroatom doped (substituted) re-flashed graphene.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] CROSS-REFERENCE TO RELATED APPLICATIONS

[0002] This application claims priority to U.S. Patent Application Serial No. 63 / 341,934, filed on May 13, 2022, entitled “Flash Joule Heating for Production Of 1D Carbon And / Or Boron Nitride Nanomaterials, 1D Materials Integrated With 0D, 1D, 2D, And 3D Nanomaterials, Composites, Nanostructures, Networks, Or Mixtures Thereof”, which is commonly owned by the owner of the present invention. The entire contents of this patent application are hereby incorporated by reference. Technical Field

[0003] The present invention relates to flash Joule heating for preparing 1D carbon and / or boron nitride nanomaterials, 1D materials, their combination with 0D, 1D, 2D and 3D nanomaterials, composites, nanostructures, networks, doped or substituted materials, and mixtures thereof.

[0004] Statement Regarding Federally Funded Research

[0005] This invention was made with government support under Grant No. FA9550-22-1-0526 from the United States Air Force Office of Scientific Research, Grant No. FE0031794 from the National Science Foundation (Graduate Research Fellowship), and Grant No. ERDC No. W912HZ-21-2-0050 from the US Army Corp. of Engineers. The U.S. Government has certain rights in this invention.

[0006] Statement Regarding Federally Funded Research

[0007] This invention was made with government support under Grant No. FA9550-22-1-0526 awarded by the Air Force Office of Scientific Research, Grant No. FE0031794 awarded by the National Science Foundation, and Grant No. W912HZ-21-2-0050 awarded by the Army Corp. of Engineers. The U.S. Government has certain rights in this invention. Background Art

[0008] One-dimensional (1D) carbon materials. One-dimensional (1D) carbon materials have received a great deal of research and attention since their discovery in the late 20th century. [Ajayan 2001; Rathinavel 2021; Ruiz-Cornejo 2020; Yang 2015]. Although carbon nanotubes represent the most widely recognized example of such 1D materials, many subclasses and different morphologies have been characterized. [Shi 2019; KOU 2017]. Examples of these 1D carbon nanomaterials include single-walled and multi-walled carbon nanotubes (CNTs), as well as ribbon- and sheet-like carbon nanofibers, bamboo-like carbon nanotubes, cup-stacked carbon nanofibers, etc. [Feng 2014; Jai 2017; Liu 2021; Wang 2019]. 1D materials are widely used in composites, coatings, sensors, electrochemical energy storage, and electrocatalysts, taking advantage of their strength, electrical conductivity, low density, broadband electromagnetic absorption, high surface area, and chemical robustness. [Restivo 2020; Kumar 2021; Kour 2020; Wu 2021]. Due to their widespread use and scientific interest, identifying new methods for synthesizing 1D carbon materials remains critical. Most synthetic strategies to form 1D carbon materials (including arc discharge, laser ablation, chemical vapor deposition, plasma torches, and high partial pressure carbon monoxide) involve the migration of carbon atoms in the feedstock onto a catalytic metal surface, which then grows into a graphitic 1D morphology. [Xu 2019]. These existing methods typically produce a mixture of 1D materials and amorphous carbon that need to be separated, and 1D material syntheses typically have a high yield of <1 g h -1 The defect of low productivity. [Lee S 2021; McLean2021; Rao 2018].

[0009] Inspired by the low cost and high availability of feedstocks, several recent efforts have focused on converting waste plastics into higher-value carbon nanomaterials. [Yaqoob 2022; Wang 2020; Williams 2021]. However, these approaches typically use a two-step chemical vapor deposition pyrolysis process: The first stage deconstructs the plastic into volatile hydrocarbons at 700-900 °C under an inert atmosphere for 0.5-2 hours. [Zhuo 2014; Sharma 2020]. In the second stage, the hydrocarbon gas then grows into 1D materials on a composite transition metal catalyst, again under an inert atmosphere at similarly high temperatures for many hours. [Wang 2022; Bazargan 2012; Gong 2013]. Growing the catalysts typically requires dedicated synthetic or templating methods, which can be time-, energy-, and resource-intensive. [Jie 2020; Ahamed 2020; Jia 2022].

[0010] Furthermore, many of these methods use a 1:1 ratio of waste plastic to grow metal complexes, meaning that every ton of waste plastic processed would require the manufacture of 1 ton of metal complex, which would hamper widespread implementation and economic feasibility. [Cai 2021]. To the best of the applicant's knowledge, the production of complex carbon hybrid materials from waste plastics has not yet been demonstrated. Current methods for producing carbon nanomaterials from waste plastics are hampered by long reaction durations and high resource consumption, large amounts of metal complex additives, and minimal scale scalability of chemical vapor deposition techniques.

[0011] Flash Joule Heating (FJH) Synthesis . Flash Joule heating (FJH) has recently been used as an efficient method for the solvent-free synthesis of various carbonaceous and inorganic nanomaterials. [Luong 2020; Wyss I 2022; Yao 2016; Deng 2022; Guo2022]. In particular, FJH has proposed a facile method to upcycle low-value waste materials into high-value nanomaterials. [Algozeeb 2020; Wyss I 2021; Advincula 2021; Wyss II 2021]. For the FJH synthesis of graphene, electrical energy and resistance are used to rapidly generate high temperatures and form mixed-layer or rotationally mismatched graphene because the short duration of FJH (0.05 to 1 second) restricts rotational movement. Reaching temperatures of >3,100 K within milliseconds allows amorphous carbon bonds to reorganize into highly ordered sp 2Hybrid sheets. [Wyss I 2022]. Flash graphene sheets form via an “active carbon” mechanism, where temperatures generated by high-resistance junctions within the sample allow annealing and formation of crystalline nanoparticles. [Stanford 2020]. The capacitive density of the reaction can also control the reaction conditions; increasing the charge per unit mass changes the nucleation process from reaction-limited to diffusion-controlled reaction kinetics. [Algozeeb 2020; Beckham 2022].

[0012] Boron Nitride Nanotubes (BNNT) Boron nitride (BN) is a very attractive III-V compound due to its superior properties, including high thermal conductivity [Terao 2010; Zeng 2017], stability [Zhu I 2005; Lee 2016], excellent mechanical strength [Chen 2017; Lahiri 2010], and insulating ability [Zh 2009]. The two most studied BN allotropes are one-dimensional (1D) boron nitride nanotubes (BNNTs) and two-dimensional (2D) hexagonal BN (h-BN). BNNTs are considered to be structural analogs of CNTs, in which carbon atoms are replaced by alternating boron and nitrogen atoms. This substitution enhances the oxidation resistance of the nanotubes in air and leads to stronger interactions with polymers compared to CNTs. [Huang 2011; Chen 2015].

[0013] In 1994, Rubio et al. theoretically predicted the existence of BNNTs [Ruio 1994], which were later synthesized by Chopra et al. using an arc discharge method in 1995 [Chopra 1995]. Since then, various methods have been used to synthesize BNNTs, including laser ablation [Yu 1998; Kim 2019; Bae 2022, ball milling combined with annealing [Chen 1999; Kim 2011; Zhuang 2016], template-assisted synthesis [Tay 2015; Wang 2008], chemical vapor deposition (CVD) [Pakdel 2012; Lourie 2000; Kim J 2018], and thermal plasma [Kim 2020; Fathalizadeh 2014].

[0014] The invention directly determines the length, diameter and purity of BNNT, which plays an important role in application. CVD is widely regarded as the most promising method for producing high-quality BNNT. The technology operates in a gas-liquid-solid (VLS) growth mechanism. [Zhi II 2005]. The yield and shape of BNNT depend greatly on the device design, gas flow, precursor and catalyst. However, CVD technology is still limited in its ability to mass-produce BNNT. The method using ball milling and annealing is recognized for its ability to produce BNNT with high yield at low cost. The BNNT prepared by this method mainly has a bamboo-like structure. Laser ablation and thermal plasma can be used to prepare BNNT with high productivity. Laser or high-temperature plasma is used as a heat source to provide high energy, so that the surface temperature of the precursor is instantly increased and vaporized to obtain thin-walled BNNT. The reaction mechanism is not clear, and a purification process is required to remove these impurities, such as B and h-BN.

[0015] Turbostratic Boron-Carbon-Nitrogen (BCN) . Canonical layered materials typically have a unique and thermodynamically favorable stacking order under standard temperature and pressure conditions. [Luong 2020; Stanford 2020]. The stacking sequence is determined by various non-covalent interactions, such as van der Waals, London, and Keesom interactions. [Smith 2011]. Deviations from these stacking morphologies lead to the formation of turbostratic lattices, which have an expansion of the intrinsic interlayer distance and a weakening of the coupling interactions between adjacent layers [Advincula 2021; Algozeeb 2020], which can introduce unique optical, electrical, and magnetic properties to turbostratic materials, thereby broadening their applications. [Wyss I2021; Chen II 2021].

[0016] The main concern for the synthesis of turbostratic materials lies in the unfavorable formation energy and spontaneous relaxation towards the thermodynamically favorable stacking sequence. Once a sustained heat source is provided, the products with the most thermodynamically stable lamellar sequence dominate, making it difficult to approach turbostratic structures. [2,8-10] [Stanford 2020; Ba 2017; Song 2010; Xu D2018]. Therefore, due to the insufficient relaxation barrier (<4 kJ mol -1 )[Rydberg 2003] and finite cooling rate (<10K s -1 ), most bottom-up methods for preparing layered materials are not applicable to the synthesis of turbostratic materials. [Chi lkoor 2020; Wang 2017]. The organization of regular in-plane configurations is usually accompanied by the formation of self-limited monolayers or well-aligned multilayer structures.

[0017] Although previous work has demonstrated that the formation of turbostratic structures can be induced by low-temperature (~500K) thermal treatment or bias-assisted hot-filament chemical vapor deposition (CVD), these products usually have a semi-crystalline in-plane structure with hybrid nanocrystals and amorphous domains. [Kakiagea 2013; Ahn 2000]. The semi-crystalline in-plane structure can prevent the precise stacking of the layers, which induces the formation of turbostratic stacking structures. In addition, guest intercalation methods using ionic liquids [Lian 2009] and chemical functionalization [Cao2022] have been used to stabilize turbostratic materials. These methods are attributed to the modification of interlayer interactions, such as π-π stacking and hydrogen bonding between adjacent basal planes. Therefore, the direct synthesis of turbostratic materials with a high degree of in-plane crystallinity remains challenging when one wants to study the unique properties arising from the weak coupling effect between adjacent layers.

[0018] This semicrystalline in-plane structure is common for multicomponent systems when starting from gaseous precursors such as boron-nitrogen binary compounds [Demirci 2020] and boron-carbon-nitrogen ternary compounds (BCN). [Ahn 2000; Puyoo 2017]. These reactive precursors, such as BCl3 and NH3 [Puyoo 2017] or ammonia borane (BH3NH3) [Zhong 2017], achieve rapid transformations and lead to the formation of amorphous products with many structural defects. Although the in-plane crystallinity of the product can be improved by controlling the annealing time and temperature, the final formation of semicrystalline structures or well-aligned stacking structures [Chilkoor 2020; Ahn 2000] is due to the thermodynamic limitations of these traditional bottom-up methods and the metastable characteristics of turbostratic materials with high in-plane crystallinity. [Luong 2020; Stanford 2020].

[0019] Turbostrates in 2D materials have interlayer unalignment. The lack of alignment expands the intrinsic interlayer distance and weakens the optical and electronic interactions between adjacent layers. This introduces properties that are different from those of structures with well-aligned lattices and strong coupling interactions. However, the direct and rapid synthesis of turbostratic materials remains a challenge due to their thermodynamically metastable nature.

[0020] Doped graphene. Graphene is a 2D material with exceptionally high mechanical strength, electrical conductivity, and other desirable chemical properties. [Ye 2019]. Graphene is often doped (or the term "substituted" may be used, as the substituted or added atoms may be above 5 wt%) with non-carbon atoms to chemically modify the graphene and adjust its chemical, physical, and optical properties. [Wang 2014; Xu H 2018; Agnoli 2016]. These atoms may be placed in the graphene lattice, and are therefore most often similar to carbon atoms in atomic radius, or added above and below the position of the graphene lattice, such as in the addition of fluorine atoms. The resulting lattice typically contains up to a few percent of heteroatoms in atomic ratio. In 2020, a prominent technique for the mass production of graphene, called flash Joule heating (FJH), was disclosed, by which amorphous carbon compounds can be converted into turbostratic graphene using electric pulses. [Luong 2020]. Amorphous carbon can be derived from a variety of sources, including coal products, waste plastics [Wyss II 2022; Wyss III 2022; Wyss I 2021], and rubber waste [Advincula 2021]. In 2022, an article was published that presents mixing an amorphous carbon feedstock with an organic feedstock containing non-carbon atoms (such as melamine and boric acid) and flashing these feedstocks together to prepare heteroatom (non-carbon) doped flash graphene. [Chen 2022]

[0021] In this previously reported technique, an organic heteroatom feedstock is destroyed along with an amorphous carbon feedstock. During the subsequent graphene formation, the non-carbon heteroatoms previously present in these feedstocks place themselves within the graphene structure or above and below the plane, so that the product is doped graphene. The amount of non-carbon heteroatoms present in the graphene lattice is described in terms of doping percentage, which is the atomic percentage of the graphene lattice that contains non-carbon atoms. By this method, doping percentages of up to 7.4% for single dopant flash were achieved in the graphene lattice with sulfur, nitrogen, boron and fluorine atoms in different experiments, and slightly higher doping rates were achieved by using combinations of these dopants simultaneously. Summary of the invention

[0022] The present invention relates to flash Joule heating (FJH) for preparing one-dimensional (1D) carbon and / or boron nitride nanomaterials, as well as 1D materials, which are combined with 0D, 1D, 2D and 3D nanomaterials, their composites, nanostructures, networks and mixtures. Such materials produced by FJH include 1D carbon and hybrid nanomaterials, boron nitride nanotubes (BNNTs), turbostratic boron-carbon-nitrogen (BCN), doped (substituted) graphene and heteroatom-doped (substituted) re-flash graphene.

[0023] In general, in one embodiment, the invention features a method that includes flash Joule heating a mixture of a material and a catalyst to form a 1-dimensional structure.

[0024] Implementations of the invention may include one or more of the following features:

[0025] Flash Joule heating can be a process that includes applying a voltage across a mixture, which drives a current through the mixture to form a 1-dimensional structure. The voltage can be applied in one or more voltage pulses. The duration of each of the one or more voltage pulses can be a duration period.

[0026] The material may be a carbon material that is not substantially graphene.

[0027] The 1D structure can be graphite 1D and / or hybrid material nanomaterial.

[0028] The method may also include forming a 1-dimensional structure and one or more other dimensional structures selected from a 0-dimensional structure, a 2-dimensional structure, and a mixture thereof.

[0029] The 1-dimensional structure and one or more other dimensional structures may be covalently or non-covalently bound.

[0030] A 1-dimensional structure and one or more other dimensional structures can be combined to form a 3-dimensional network.

[0031] The material may be a carbon material including a polymer.

[0032] The mixture may be formed by supporting the polymer with the catalyst particles by surface wetting.

[0033] The mixture may be formed by melt mixing the polymer supported with the catalyst particles.

[0034] The material may be a waste product including carbon.

[0035] The catalyst may be selected from iron(II) chloride, nickel(II) chloride, cobalt(II) chloride and ferrocene.

[0036] The catalyst may be selected from any transition metal or main group metal or transition metal or main group metal complex, salt, oxide, halide or combination thereof.

[0037] The mixture may further include a conductive carbon additive.

[0038] The conductive carbon additive may be selected from graphene, flash graphene, turbostratic graphene, anthracite, coconut shell derived carbon, pyrotreated biochar, activated carbon, calcined petroleum coke, metallurgical coke, coke, shungite, carbon nanotubes, asphaltenes, acetylene black, carbon black, ash, carbon fibers, and mixtures thereof.

[0039] Conductive carbon additives may include carbon black and / or metallurgical coke.

[0040] After the flash Joule heating, the method may further include separating at least some of the conductive carbon additive from the formed 1-dimensional structure.

[0041] The separation step may be based on the grain size of the conductive carbon additive and the size of the formed 1-dimensional structure.

[0042] The separation step may include sieving to separate the small 1-dimensional structures from the large particle conductive carbon additive.

[0043] After the separation step, the % yield of the 1-dimensional structures formed in the process may be at least 80%.

[0044] After the separation step, the % yield of the 1-dimensional structures formed in this process may be between 80% and 90%.

[0045] The % yield of the 1-dimensional structures formed in the process may be at least 65%.

[0046] The % yield of the 1-dimensional structures formed in the process may be at least 80%.

[0047] In general, in another embodiment, the invention features a 1-dimensional structure made by any of the above methods.

[0048] Implementations of the invention may include one or more of the following features:

[0049] The 1-dimensional structure may be any form of nanostructure or microstructure, wherein the length of the 1-dimensional structure is at least 3 times the width of the 1-dimensional structure.

[0050] 1D structures may not be a single atomic sheet thick.

[0051] In general, in another embodiment, the invention features a composite that includes any of the above-described 1-dimensional structures.

[0052] Implementations of the invention may include one or more of the following features:

[0053] The composite may include a 1-dimensional structure and a vinyl ester.

[0054] The composite may be a 1-dimensional structure-reinforced vinyl ester resin nanocomposite.

[0055] In general, in another embodiment, the invention features a structure or network prepared by any of the methods described above.

[0056] Implementations of the invention may include one or more of the following features:

[0057] The 1-dimensional structure of the structure or network may be any form of nanostructure or microstructure, wherein the length of the 1-dimensional structure is at least 3 times the width of the 1-dimensional structure.

[0058] The 1-dimensional structure of a structure or network may not be a single atomic sheet thick.

[0059] In general, in another embodiment, the invention features a method that includes flash Joule heating a mixture to form boron nitride nanotubes. The mixture includes (i) a boron-containing material, (ii) a nitrogen-containing material, and (iii) a catalyst.

[0060] Implementations of the invention may include one or more of the following features:

[0061] Flash Joule heating can be a process that includes applying a voltage across the mixture, which drives a current through the mixture to form boron nitride nanotubes. The voltage can be applied in one or more voltage pulses. The duration of each of the one or more voltage pulses can be a duration period.

[0062] The material containing boron and the material containing nitrogen may be different materials.

[0063] The material containing boron and the material containing nitrogen are the same material.

[0064] The same material may be ammonia borane.

[0065] The catalyst may be Ni(acac)2 and / or Fe(acac)3.

[0066] The catalyst may include Ni and / or Fe.

[0067] The mixture may further include a conductive carbon source.

[0068] The conductive carbon source may be selected from graphene, flash graphene, turbostratic graphene, anthracite, coconut shell derived carbon, pyrotreated biochar, activated carbon, calcined petroleum coke, metallurgical coke, shungite, carbon nanotubes, asphaltenes, acetylene black, carbon black, ash, carbon fibers, and mixtures thereof.

[0069] The conductive carbon source may include carbon black and / or metallurgical coke.

[0070] The mixture may include (i) a boron-containing material and a nitrogen-containing material and (b) a conductive carbon source in a weight ratio between 1:2 and 2:1.

[0071] After the flash Joule heating, the method can further include separating at least some of the conductive carbon source from the formed boron nitride nanotubes.

[0072] The separation step can be based on the particle size of the conductive carbon source and the size of the boron nitride nanotubes formed.

[0073] The separation step may include sieving to separate the small boron nitride nanotubes from the large particles of the conductive carbon source.

[0074] After the separation step, the % yield of the boron nitride nanotubes formed in the method may be at least 45%.

[0075] After the separation step, the % yield of the 1-dimensional structures formed in the process may be at least 60%.

[0076] The % yield of boron nitride nanotubes formed in the method may be at least 45%.

[0077] The % yield of boron nitride nanotubes formed in the method may be at least 60%.

[0078] The n products of the method may include boron nitride nanotubes and sheet-like structures.

[0079] At least 30% of the product of the method may be boron nitride nanotubes.

[0080] In general, in another embodiment, the invention features a composition including boron nitride nanotubes prepared by any of the methods described above.

[0081] Generally, in another embodiment, the invention features a method comprising flashing a Joule heated mixture to form a turbostratic nanomaterial comprising (a) boron, (b) nitrogen, and (c) a third element selected from carbon, tungsten, or iron. The mixture comprises (i) a material comprising boron, (ii) a material comprising nitrogen, and (iii) a material comprising the third element.

[0082] Implementations of the invention may include one or more of the following features:

[0083] Flash Joule heating can be a process comprising applying a voltage across the mixture, which drives a current through the mixture to form a turbostratic nanomaterial. The voltage can be applied in one or more voltage pulses. The duration of each of the one or more voltage pulses can be a duration period.

[0084] The third element may be carbon, and the turbostratic nanomaterial may be turbostratic BCN.

[0085] The third element may be tungsten, and the turbostratic nanomaterial may be turbostratic BN-W.

[0086] The third element may be iron, and the turbostratic nanomaterial may be turbostratic BN-Fe.

[0087] The mixture may include (i) a material including boron and a material including nitrogen and (b) a material including a third element in a weight ratio higher than 4:1.

[0088] The mixture includes (i) a material including boron and a material including nitrogen and (b) a material including a third element in a weight ratio between 1:2 and 2:1.

[0089] The % yield of turbostratic nanomaterial formed in the method may be at least 20%.

[0090] The % yield of turbostratic nanomaterial formed in the method may be at least 30%.

[0091] Generally, in another embodiment, the invention features a composition comprising a turbostratic nanomaterial comprising (a) boron, (b) nitrogen, and (c) a third element selected from carbon, tungsten, and iron. The composition is prepared by any of the above methods.

[0092] Generally, in another embodiment, the invention is characterized in that a method for forming doped or substituted graphene is used. The method includes performing a first flash Joule heating process with a first mixture to form a first formed graphene. The first mixture includes (i) a carbon source that is not substantially graphene and (ii) a catalyst. The method further includes mixing one or more heteroatom doped compounds with the first formed graphene to form a second mixture. The method further includes performing a second flash Joule heating process with the second mixture to form a doped or substituted graphene.

[0093] Implementations of the invention may include one or more of the following features:

[0094] The first flash Joule heating process may include applying a first voltage across the first mixture, which drives a first current through the first mixture to form a first formed graphene. The first voltage may be applied with one or more first voltage pulses. The duration of each of the one or more first voltage pulses may be a first duration period. The second flash Joule heating process may include applying a second voltage across the second mixture, which drives a second current through the second mixture to form a doped or substituted graphene. The second voltage may be applied with one or more second voltage pulses. The duration of each of the one or more second voltage pulses may be a second duration period.

[0095] The first formed graphene may be a 1-dimensional structure.

[0096] The 1-dimensional structure can be formed by any of the above methods.

[0097] The first formed graphene may be graphene having holes and wrinkles.

[0098] The first formed graphene may be turbostratic graphene.

[0099] The carbon material may include a polymer.

[0100] The carbon material may be a waste product including carbon.

[0101] The carbon material may be plastic.

[0102] The carbon material may be selected from graphene, flash graphene, turbostratic graphene, anthracite, coconut shell derived carbon, pyrotreated biochar, activated carbon, calcined petroleum coke, metallurgical coke, shungite, carbon nanotubes, asphaltenes, acetylene black, carbon black, ash, carbon fibers, and mixtures thereof.

[0103] The conductive carbon material may include metallurgical coke and / or asphaltenic activated carbon.

[0104] The catalyst may be selected from iron(II) chloride, nickel(II) chloride, cobalt(II) chloride and ferrocene.

[0105] The catalyst may be selected from any transition metal or main group metal or transition metal or main group metal complex, salt, oxide, halide or combination thereof.

[0106] After the first flash Joule heating process, the method may further include separating at least some of the carbon material from the formed first formed graphene.

[0107] The separation step may be based on the particle size of the carbon material and the size of the first formed graphene.

[0108] The separating step may include sieving to separate the small first-formed graphenes from the large particle carbon material.

[0109] The step of mixing to form a second mixture may include mixing exactly one heteroatom doping compound with the first formed graphene.

[0110] The step of mixing to form a second mixture may include mixing two or more heteroatom doping compounds with the first formed graphene.

[0111] The one or more heteroatom dopant compounds may each contain at least one heteroatom selected from boron, nitrogen, sulfur, and fluorine.

[0112] The one or more heteroatom doping compounds may be independently selected from boric acid, melamine resin, polyphenylene sulfide, and perfluorooctanoic acid.

[0113] The one or more heteroatom doping compounds may include an organic powder having a low melting point.

[0114] The ratio of (i) the one or more heteroatom doping compounds to (ii) the first-formed graphene may be in a weight ratio of 1:8 to 1:2.

[0115] The second flash Joule heating process may be performed under an argon atmosphere.

[0116] The carbon source may have a large particle size.

[0117] The second flash Joule heating process may be performed using a first second flash Joule heating voltage and a second second flash Joule heating voltage. The second second flash Joule heating voltage may be greater than the first second flash Joule heating voltage.

[0118] The voltage of the second flash Joule heating may be at least twice the voltage of the first flash Joule heating.

[0119] The voltage of the second flash Joule heating may be at least five times the voltage of the first flash Joule heating.

[0120] The second flash Joule heating process may be performed with pulse width modulated DC electrical pulses discharged from the capacitor bank.

[0121] The second flash Joule heating process can be performed with modulated or unmodulated AC and DC current sources.

[0122] The first flash Joule heating process may be performed in a first cylindrical reactor having a first diameter. The second flash Joule heating process may be performed in a second cylindrical reactor having a second diameter. The first reactor may be larger than the second reactor.

[0123] Doped or substituted graphene may include heteroatoms doped into the graphene lattice.

[0124] Doped or substituted graphene may include heteroatoms above or below the graphene lattice.

[0125] Doped or substituted graphene can include heteroatoms doped into the graphene lattice and heteroatoms above or below the graphene lattice.

[0126] The doping rate of the doped or substituted graphene may be at least 10%.

[0127] The doping rate of the doped or substituted graphene may be at least 20%.

[0128] In general, in another embodiment, the invention features a doped or substituted graphene prepared by any of the above methods.

[0129] In general, in another embodiment, the invention features a method that includes mixing any of the above-described doped or substituted graphenes in concrete to increase the mechanical strength of the concrete.

[0130] In general, in another embodiment, the invention features a concrete including any of the above-described doped or substituted graphenes.

[0131] In general, in another embodiment, the invention features a method that includes mixing any of the above-described doped or substituted graphenes in an epoxy resin to increase the mechanical strength of concrete.

[0132] In general, in another embodiment, the invention features an epoxy resin that includes any of the above-described doped or substituted graphenes.

[0133] In general, in another embodiment, the invention features a battery having a battery electrode that includes any of the above-described doped or substituted graphenes. BRIEF DESCRIPTION OF THE DRAWINGS

[0134] Figures 1A-1F Shown is the preparation of flash 1D material (F1DM). Figure 1A is a schematic diagram of the FJH process for forming F1DM, with a representative scanning electron microscope (SEM) image showing the carbon-rich F1DM region of the sample. Figure 1B-1C is an SEM image of the F1DM-rich region within the sample, showing the entangled arrangement of the resulting 1D material. TEM images of different F1DM morphologies, including ribbon-type nanofibers ( Figure 1D )、Bamboo nanofibers( Figure 1E ) and multi-walled nanotubes ( Figure 1F ). The lattice fringes are highlighted with yellow lines to help guide the eye, and the average interlayer spacing for each morphology is also provided. Figure 1F Fast Fourier transform of the nanotube, showing the prominent (002) stripes. The scale bar in the image corresponds to (i). Figure 1A 5μm, (ii) Figure 1B 3μm, (iii) Figure 1C 300nm, and (iv) Figures 1D-1F 10nm.

[0135] Figures 2A-2F Characterization of F1DM synthesized from virgin HDPE powder is shown. Figure 2A Shown are representative high-resolution extended Raman spectra of the F1DM sample compared to a control sample with no metal introduced but all FJH parameters being the same. Figure 2B The Raman spectra of the F1DM sample and the control sample are compared, showing the Raman spectra from 36 μm 2 The radial breathing mode peaks are absent in the average Raman spectra of the region and in the control sample. Figure 2C is a comparison of the high resolution Raman spectra of the M, TS1, and TS2 peaks in the F1DM sample and the control sample, showing the presence of the M peak only in the F1DM sample. Figure 2Dis a powder XRD comparing F1DM with the starting material and a control sample where no metal catalyst was used but all other parameters were the same. Figure 2E is a powder XRD spectrum comparing the (002) peaks of F1DM and control samples, showing the multi-Lorentzian peaks of F1DM. Figure 2F is a powder XRD spectrum showing the (101) and (100) peak areas, showing an enhanced (101) peak in the F1DM sample.

[0136] Figures 3A-3F Characterization of F1DM synthesized from post-consumer mixed waste plastics is shown. Figure 3A is a Raman spectrum showing that F1DM derived from mixed waste plastics is characterized by a large area Raman average spectrum. Figure 3B Powder XRD comparing waste plastics and synthesized F1DM. Figure 3C It is a survey and high resolution XPS. Figure 3D-3F is a SEM image showing the morphology of waste plastic-derived F1DM.

[0137] Figures 4A-4I Electron microscopy images showing the regions colocalizing to form 1D and 2D morphologies of graphitic hybrid materials and molecular dynamics models are shown. Figures 4A-4D is a SEM image showing the colocalization and coalescence of 1D and 2D graphitic materials, where 2D morphologies are attached to the ends of 1D morphologies. Figure 4E is a TEM image showing the region where bamboo-like carbon nanofibers are colocalized with the edge of a graphene sheet. Figure 4F yes Figure 4F High-resolution TEM image of the highlighted area. Figure 4G TEM image of bamboo-like nanofibers fused with graphene sheets. Figure 4H yes Figure 4G Atomic-resolution bright-field TEM image of the highlighted area. Fig. 4I is the fast Fourier transform, showing Figure 4H AB stacking in the hybrid material shown. Figure 4A The scale bars in the figure correspond to (i) 20 μm, (ii) Figure 4B-4C The scale bar in (iii) corresponds to 3 μm. Figure 4D The scale bar in (iv) corresponds to 1 μm. Figures 4E-4F The scale bar in (v) corresponds to 20 nm. Figure 4G The scale bar in (vi) corresponds to 100 nm. Figure 4H The scale bar in the figure corresponds to

[0138] Figures 5A-5IQuantitative analysis of size and morphology control by adjustment of FJH parameters is shown. Figures 5A-5D are confidence interval plots, respectively examining the effects of (a) catalyst species, (b) catalyst concentration in the wetting solution, (c) peak voltage during FJH, and (d) capacitance density applied during FJH on the diameter of F1DM, as determined from SEM images. The mean diameter is shown by the points and the 95% confidence interval is shown by the error bars. Lines connecting the mean values ​​for each sample are provided to guide the eye. Figure 5E-5H are stacked bar graphs examining the effects of (e) catalyst species, (f) catalyst concentration in the wetting solution, (g) discharge voltage applied during FJH, and (h) capacitance density applied during FJH on the morphology of F1DM, as determined from SEM images. Fig.5I The following are stacked bar graphs examining the morphological composition of the sample used in the vinyl ester composite; the sample obtained after sieving; and the sample obtained from two replicate blends. Figures 5A-5D Each data point in represents 120 individual carbon nanofibers or nanotubes from 6 randomly selected sample areas to ensure accurate average values. Figure 5E-5I In the study, 108 randomly selected areas (12 images, each divided into 9 areas of equal area) of each sample were imaged and assigned the dominant morphology, i.e., 1D, 2D, or hybrid. The optimized parameter that maximized the share of 1D and hybrid morphologies was 0.1 g mL -1 Fe(III), discharge at 200 V, capacitance density 1.46 mF mg -1 .

[0139] Figures 6A-6D Atomistic simulations of amorphous carbon annealed at 3000 K in contact with Ni nanoparticles are shown. Fig. 6A shows the structure after initial pre-annealing, while Figure 6B The final structure is shown, showing the initiation of carbon fiber formation through carbon interactions and catalytic graphitization. Figure 6C The graphitization levels of all carbon and Ni-affected carbon are shown. Fig.6D The percentage of carbon affected by the Ni particles throughout the simulation is shown.

[0140] Figures 7A-7F The application of F1DM in the composite and quantitative comparison of sustainability with commercial alternatives are shown. Figure 7A-7B Mechanical analysis of vinyl ester nanocomposites reinforced with F1DM compared with commercial multi-walled carbon nanotubes (MWCNTs) in (a) large-scale compression tests and mechanical analysis of vinyl ester nanocomposites reinforced with F1DM compared with neat matrix materials in (b) tensile tests are shown, respectively. Figure 7C-7EThe (c) cumulative energy requirement, (d) overall warming potential, and (e) cumulative water usage associated with the F1DM synthesis via surface wetting or melt-mixing catalyst loading strategies compared with the FJH synthesis of 2D flash graphene without the need for metal catalysts are shown, respectively. Figure 7F A comparison of two FJH syntheses of F1DM strategies considered in life cycle assessments compared to literature life cycle assessments probing carbon nanotube or nanofiber synthesis is shown.

[0141] Figures 8A-8G Shown are mechanical testing of F1DM and vinyl ester epoxy composites compared to 50 nm diameter commercial MWCNTs obtained from Cheap Tubes (5% CheapTubes) and 2D flash graphene synthesized by FJH. Figures 8A-8C shows a nanoscale compression test, Figures 8D-8E shows a macro-scale compression test, Figure 8F-8G A macroscale tensile test is shown.

[0142] Figures 9A-9D Shows Figures 8A-8G Representative stress-strain curves of mechanical testing are shown. Fig. 9A shows a nanoscale compression test, Figure 9B-9C shows a macro-scale compression test, Fig.9D A macroscale tensile test is shown.

[0143] Figures 10A-10C is a schematic representation of the life cycle inventory of the considered FH options for the synthesis of F1DM compared with the main industrial methods. Fig. 10A A flow chart showing a general business process, Fig. 10B A flow chart showing melt mixing of F1DM and FJH, and Fig. 10C Flowchart showing the surface wetting of F1DM and FJH.

[0144] Figures 11A-11E The synthesis of boron nitride nanotubes (BNNTs) by flash Joule heating is shown. Fig.11A Schematic diagram of the FJH apparatus and the production of BNNTs from ammonia borane (AB) precursor. Fig. 11B is the temperature measurement curve of the sample in the FJH process. Fig. 11C is the conversion rate of AB in melt mixing and FJH process. Figures 11D-11E is a photograph of a flash evaporation apparatus having a quartz tube and a polyetheretherketone (PEEK) tube.

[0145] Figures 12A-12D Characterization of BNNTs synthesized by FJH is shown. Fig. 12A are the FTIR spectra of AB precursor and flash product. Fig. 12Bare the Raman spectra of AB precursor and flash product. Fig. 12C It is the XRD pattern of AB precursor and flash product. Fig.12D are the B1s spectra of the AB precursor and the flash product.

[0146] Figures 13A-13I is a SEM image of BNNT product formation. Figures 13A-13C is a SEM image of BNNTs formed in a quartz tube. Figures 13D-13F is a SEM image of BNNT formation in PEEK tube. Figure 13G is a low magnification SEM image of the tube-enriched area. Fig.13H is a low magnification SEM image of the plate-enriched area. Fig.13I is a SEM image of BN sheet formation in a quartz tube.

[0147] Figures 14A-14K is an image of BNNTs in the flash product. Figures 14A-14E is a TEM image of BNNTs and BN sheets formed in a quartz tube. Fig.14F is the HAADF-STEM image and the corresponding element distribution of BNNTs. Figures 14G-14H is the HAADF-STEM image and the corresponding element distribution of the BN sheet. Fig.14I is a TEM image of the catalyst particles. Figures 14J-14K is the HAADF-STEM image and the corresponding element distribution of the BNNT bamboo structure.

[0148] Figures 15A-15D An all-solid-state synthesis of f-BCN via flash Joule heating is shown. Fig.15A Schematic diagram of the formation of f-BCN from BH3NH3 and carbon via FJH. Fig. 15B Real-time temperature measurements from the sample during the FJH process are shown. Fig. 15C is a time-temperature-conversion diagram showing the ultrafast cooling (>10 3 K.s -1 )'s dynamic formation of the turbostratic structure. Fig.15D Figure 2 is a plot of the potential energy distribution of h-BN sheets of various sizes (per atom) along the rotational minimum energy path from AA' to AB stacking.

[0149] Figures 16A-16J Shown are the spectral analysis and crystal structure of f-BN. Fig.16A FTIR spectra of BH3NH3, f-BN and commercial h-BN. Fig. 16B These are the Raman spectra of BH3NH3 and f-BN. Fig. 16C is the E reported for f-BN and commercial h-BN 2gRepresentative high-resolution Raman spectra of peak positions. Fig.16D It is about f-BN and commercial h-BN E 2g Statistical investigation of peak positions. Number of samples N=100. Fig.16E is a schematic diagram showing the structures of h-BN and t-BN. Fig.16F are the XRD spectra of f-BN and commercial h-BN. Figures 16G-16H are high-resolution XPS spectra of commercial h-BN and f-BN. Figure 16G is the B1s spectrum, Fig.16H It is the N1s spectrum. Fig.16I is the HR-TEM image of f-BN sheet. Fig.16J are the BF-STEM, HAADF-STEM images and the corresponding element distribution of f-BN sheets.

[0150] Figures 17A-17I Mechanical peeling test of f-BN is shown. Figures 17A-17B are SEM images showing the stripping results of (a) f-BN and (b) commercial h-BN, respectively. Fig. 17C The size distribution of f-BN and commercial h-BN by the tape exfoliation method is shown. The number of samples N=100. Figures 17D-17E are SEM images showing the uniaxial mechanical shearing results of (d) f-BN and (e) commercial h-BN, respectively. Fig.17F The size distribution of f-BN and commercial h-BN by uniaxial mechanical shearing method is shown. Number of samples N=100. Figures 17G-17H TEM images of (g) f-BN and (h) commercial h-BN after bath sonication, respectively, both on ribbon carbon grids. Fig.17I The layer number distribution of f-BN treated by bath sonication is shown. Number of samples N=16.

[0151] Figures 18A-18D The electrochemical corrosion resistance test of f-BN composite is shown. Figures 18A-18B (a) Bode plots and (b) Tafel plots of electrochemical analysis of bare Cu, Cu-PVA, Cu-PVA-h-BN, and Cu-PVA-f-BN in 3.5 wt% NaCl(aq), respectively. Figures 18C-18D (c) Bode plots and (d) Tafel plots of electrochemical analysis of bare Cu, Cu-PVA, Cu-PVA-h-BN and Cu-PVA-f-BN in 0.5 M H2SO4, respectively.

[0152] Figures 19A-19DElectrochemical LPR experiments of different coating materials in 3.5 wt% NaCl(aq) for (a) bare Cu, (b) Cu-PVA, (c) Cu-PVA-h-BN and (d) Cu-PVA-f-BN are shown.

[0153] Figures 20A-20H Figure 5 shows the characterization of f-BCN with different chemical compositions. Fig. 20A is a schematic diagram of f-BCN with variable atomic ratios. Fig. 20B The elemental distribution of different f-BCN samples is shown. Fig. 20C The valence band maximum (VBM) of different f-BCN samples is shown. Fig.20D The interlayer spacing and surface area of ​​different f-BCN samples are shown. Fig.20E TEM image and Moiré pattern of f-BCN-30 are shown. Fig.20F The corresponding FFT results are shown. Figure 20G is a HR-TEM image showing the in-plane crystallinity of f-BCN-30. Fig. 20H HAADF-STEM and BF-STEM images of f-BCN-30 sheets and the corresponding element distribution. The scale bar is 20 nm.

[0154] Fig.21 Represents the boron-carbon-nitrogen ternary phase diagram before heat treatment.

[0155] Figures 22A-22B Schematic diagram of the general workflow for the synthesis of heteroatom-doped re-flashed graphene (FG) from (a) metallurgical coke (MC) and (b) asphaltene activated carbon (BAC), respectively, via flash Joule heating (FJH).

[0156] Fig.23 A schematic diagram of a flash vessel for use with an embodiment of the present invention is shown.

[0157] Figures 24A-24B Schematic diagram showing the input and output of the flash vessel. The re-flash doping process consists of two separate flash reactions ( Figures 24A-24B shown).

[0158] Figures 25A-25C Spectral analysis of N-doped BAC flash graphene is shown. Fig.25A The average of 100 Raman spectra (with standard deviation) is shown. Fig.25B A high resolution Raman spectrum is shown showing TS1 and TS2 peaks, a positive indicator of turbostraticity. Fig.25C An XPS spectrum is shown, in which the nitrogen peaks are deconvoluted based on their binding type. The nitrogen content determined here is over 5%.

[0159] Figures 26A-26C SEM images and EDX elemental analysis of N-doped flash graphene are shown.

[0160] Figures 27A-27B shows the spectral analysis of N-doped MC-reflashed graphene. Fig.27A The average of 100 Raman spectra (with standard deviation) is shown. Fig.27B B XPS spectrum is shown, where the nitrogen peaks are deconvoluted based on their binding type.

[0161] Fig.28 A summary of the re-flash doping results is shown. DETAILED DESCRIPTION

[0162] The present invention relates to flash Joule heating (FJH) for preparing one-dimensional (1D) carbon and / or boron nitride nanomaterials, as well as 1D materials, which are combined with 0D, 1D, 2D and 3D nanomaterials, composites, nanostructures, networks, and mixtures thereof. Such materials produced by FJH include 1D carbon and hybrid nanomaterials, boron nitride nanotubes (BNNTs), turbostratic boron-carbon-nitrogen (BCN), heteroatom-doped (substituted) graphene, and heteroatom-doped (substituted) re-flash graphene.

[0163] Synthesis of one-dimensional (1D) carbon and hybrid nanomaterials via FJH

[0164] In embodiments, the present invention relates to the conversion of plastics into 1D materials and hybrid graphitic 1D / 2D materials with controlled morphology. The method utilizes in situ catalysis and enables directionally controlled assembly of active carbon during FJH. The produced F1DM exhibits excellent mechanical properties in vinyl ester composites, which is attributed to the hybrid morphology and indicates the value and utility of upcycled products of waste plastics. Furthermore, when analyzed using a cradle-to-gate perspective life cycle assessment, FJH presents substantial advantages over classical 1D synthesis.

[0165] Graphite one-dimensional (1D) and hybrid nanomaterials represent powerful solutions in composite and electronic applications due to their superior properties, but large-scale synthesis of hybrid materials has not yet been achieved. The method is scalable and uses flash Joule heating (FJH) to produce graphite 1D materials from polymers. This avoids lengthy chemical vapor deposition and does not use solvents or water. Flash 1D materials (F1DM) synthesized using a variety of earth-abundant catalysts have controllable diameters and morphologies through parameter adjustment. In addition, the method can be modified to form hybrid materials in which F1DM is bound to turbostratic graphene. In nanocomposites, F1DM is superior to commercially available carbon nanotubes. Using life cycle assessment (LCA), FJH synthesis represents an 86-92% reduction in cumulative energy demand and a 92-94% reduction in overall warming potential compared to current 1D material synthesis strategies. FJH provides a cost-effective and sustainable way to upgrade waste plastics into valuable 1D and hybrid nanomaterials.

[0166] Synthetic F1DM

[0167] Flash Joule heating (FJH) has recently been recognized as an effective method for the solvent-free synthesis of carbonaceous and inorganic nanomaterials, in which electrical energy and electrical resistance are used to rapidly (0.05–3 s) generate high temperatures (~3,000 K), allowing solvent-free upcycling of low-value waste materials into high-value products. [Luong 2020; Yao 2016; Xie 2018]. Graphitic 1D and hybrid nanomaterials are typically grown by depositing active carbon on metallic nanoparticles, and FJH is known to efficiently generate active carbon, inspiring research on the growth of 1D nanomaterials using FJH.

[0168] The introduction of low concentrations of simple, earth-abundant transition metal salts into carbonaceous polymer feedstocks leads to the in situ catalyzed growth of graphitic 1D materials in a FJH process. Figure 1A Schematic diagram 101 shown in . Iron (II) chloride, nickel (II) chloride, cobalt (II) chloride and ferrocene are used as growth catalysts. The polymer feedstock is selected because of the abundance and low cost of waste plastics and the resulting FIDM yield. The resistance of the reaction mixture is easily controlled by adjusting the amount of conductive carbon additives such as carbon black or metallurgical coke. The high resistance of the plastic precursor allows many high resistance junctions between particles in the sample, resulting in high overall and local temperatures. The FJH system (and parameters) that can be utilized can be based on the system set forth and described in the Tour '642 application and the Tour '111 PCT application, with modifications as described below.

[0169] The polymer feedstock can be loaded with catalyst particles by surface wetting or melt mixing. For surface wetting, the polymer can be mixed with 0.1 g mL -1The polymer surface is coated with a small amount of catalyst by ultrasonic treatment in an aqueous alcohol solution of a salt of ferrocene, followed by filtration and drying. For solvent-free catalyst loading, melt mixing can be used, in which a metal complex such as ferrocene and a polymer with a similar melting point are mechanically mixed in the molten state without the use of a solvent. Scanning electron microscopy (SEM) image ( Figure 1A SEM images 102 and Figure 1B-1C SEM images of ) show fibers of varying diameters formed during the FJH process. A typical aspect ratio of 330 was observed, but this cannot usually be followed continuously over the entire winding length, so this may be an underestimate.

[0170] In an embodiment, the F1DM is synthesized using a flash Joule heating reactor as described in the Tour'642 application and the Tour'111 PCT application. Specifically, the catalyst-loaded polymer feed is prepared by surface wetting or melt mixing. For the surface wetting method: a solution of an 80 / 20 v / v mixture of water and ethanol is prepared, wherein the selected salt is dissolved in the solution. For example, a concentration of 0.1 g mL -1 Then, 5 g of original or waste polymer with particle size <0.1 mm was immersed in the solution and sonicated for 15 minutes. The polymer containing salt solution was vacuum filtered to remove excess salt solution. The polymer was dried at room temperature overnight to obtain a catalyst-loaded polymer with a slight color change depending on the salt used.

[0171] For the melt mixing process: Ferrocene was used as a catalyst due to its low melting point of 173°C. The heater in the melt mixer was set to 175°C and a mixture of 4.95 g of HDPE and 0.05 g of ferrocene was melt mixed to homogeneity using a Braebender 350-E heated zone melt mixer. The molten mixture was then cooled to room temperature and ground into a fine powder using an electric hammer mill.

[0172] The catalyst-loaded polymer obtained by surface wetting or melt mixing is then mixed with the conductive additive. Amorphous carbon black (Cabot) was used for all samples here, unless metallurgical coke was specified as a cheaper alternative.

[0173] When using amorphous carbon black as a conductive additive, 20 wt% is ground together with 80 wt% of the catalyst-loaded polymer. Due to the small particle size of amorphous carbon black, it coats the polymer evenly. It is an alternative raw material to waste plastics, namely metallurgical coke, which is priced at $150 per ton. -1 The higher cost of the coal-derived product, carbon black, has also been shown to be effective.

[0174] Since metallurgical coke has a larger particle size of ~150 μm, a higher weight percentage must be used to achieve similar final sample conductivity. For the use of metallurgical coke as a conductive additive, 40 wt% was used and mixed with 60 wt% of the catalyst-loaded polymer. The particle size of both the polymer and the conductive additive may affect the ratio of the polymer raw material and the conductive additive. The conductive additive and polymer were manually mixed using a mortar and pestle. Then, 0.20 g of the homogeneous mixture was loaded into a quartz tube with an inner diameter of 8 mm and the sample was pressed into the tube with a graphite electrode to contain the powder.

[0175] The sample is then loaded into a FJH reactor and a capacitor is connected to enable discharge through the resistive sample. An initial sample resistance of 6-8Ω is used for samples as described here. The sample is loaded into a vacuum desiccator at ~20mmHg to facilitate degassing of heteroatoms and volatiles. Then, using the desired capacitance, a FJH current discharge pulse of the desired voltage is discharged through the sample to completion, lasting 1-3s, depending on the voltage and capacitance, with higher capacitance resulting in longer durations. The circuit is fully closed for 5 seconds, with a typical discharge lasting only 1-3 seconds. The voltage on the capacitor is fully discharged, which may require multiple discharges. Bright flashes can be observed from the sample due to the generation of black body radiation.

[0176] After FJH, the resistance of the sample decreased to 0.6-1Ω. The F1DM was then emptied from the quartz tube, ground using a mortar and pestle, and characterized without further purification. The yield range of F1DM (40-60 wt% of the reactants recovered as graphite product) depends on the parameters, polymer type, particle size, and the amount of conductive additive used.

[0177] Quantitative differentiation between graphitic carbon morphologies can be a difficult task, because by commonly used analytical methods, such as XPS and TGA, 1-D and 2-D morphologies look almost the same, while Raman and powder XRD only show small differences. Due to the combination of morphologies obtained during FJH, extensive SEM imaging is used to determine the morphological share of each sample. At low magnification, 1D and 2D morphologies can look similar, so for each sample, 108 different images on 9 different areas were checked and the dominant morphology (1D, 2D or hybrid) was assigned. This allows quantitative determination of the morphological percentage in area %. When discussing F1DM morphological yields, area % is used here. The maximum value of ~ 65% of the solid product is 1D morphology, and the rest includes 2D turbostratic graphene. Figures 1D-1FShown the high-resolution TEM images of ribbon carbon nanofiber, graphite bamboo carbon and multi-walled carbon nanotube.The bamboo carbon nanofiber with multilayer stacked in a cup-like manner comprises the dominant F1DM morphology.The 2D morphology present by TEM imaging observation.Observe graphene nanoribbon by TEM imaging, which can be produced by the high temperature unzipping of carbon nanotube.

[0178] Characterization of F1DM

[0179] F1DM was characterized using Raman spectroscopy mapping, which showed a high degree of graphitic character over a large area. F1DM was compared to a control sample, which contained no metal but all other conditions were the same, and both samples produced a product with 97-98% graphitic character. The graphite content was determined by three different characterization methods, including Raman spectroscopy, TGA, and high-resolution XPS. 2 100 unique spectra were collected over the area for wide area Raman mapping, which was then processed using a MatLab script that characterizes spectra with I2D / IG ratios > 0.3 as graphite. TGA can be used to determine graphitization by measuring thermal stability masses at 550 °C under air atmosphere, as amorphous carbon will degrade below this temperature. High resolution XPS and fitting of the C1s peak allow for determination of graphitic properties, and more precise methods of C KLL XPS can also probe graphite content.

[0180] High-resolution, extended exposure scans revealed the presence of radial breathing mode peaks, indicating the presence of carbon nanotubes in the F1DM sample, but not in the metal-free control sample. Figure 2A (The curves for control (no catalyst) and F1DM are 201-202, respectively); Figure 2B (The curves for the control (no catalyst) and F1DM are 211-212, respectively). By changing the Raman excitation wavelength, different radial breathing mode peaks can be observed. Low intensity M, TS1 and TS2 peaks can also be observed. Figure 2C (The curves for control (no catalyst) and F1DM are 221-222 respectively).

[0181] Located at 1750cm -1 The M peaks of α and β represent ordered AB stacking. [Ferrari 2013]. They are located at 1875 cm -1 and 2050cm -1The TS1 and TS2 peaks indicate disordered turbostratic stacking. [Merlen 2017; Chen I 2021]. The presence of both M and TS peaks indicates the presence of aligned and unaligned stacking of graphitic domains. Flash graphene is turbostratic, so the presence of the M peak is unexpected. [Luong 2020; Wyss I 20222]. Catalytically synthesized plate-like and ribbon-like carbon nanofibers typically show rotationally ordered AB stacking, which can explain the presence of the M peak and further indicate the presence of a large number of nanofiber morphologies in F1DM. [Carozo 2011; Brar 2002].

[0182] To characterize bulk FIDM products, powder X-ray diffraction (XRD) was used. Figure 2D (The curves for the starting material, control (no catalyst) and F1DM are 231-233, respectively). This shows a broad, strong and multiple Lorentzian (002) peak, indicating a graphitic structure. The F1DM (002) peak is fitted by two different Lorentzian peaks, occurring at 26.46° and 26.11°. See Figure 2E (The curves for the control (no catalyst) and F1DM are 241-242, respectively). The (002) peak of the control sample without catalyst is fit with a single Lorentzian peak centered at 26.12°. Graphitic 1D materials, such as MWCNTs and CNFs have almost identical diffraction patterns as 2D graphene because they share the same unit cell. The only difference is the interlayer spacing of turbostratic graphene (0.35nm) compared to the interlayer spacing of graphitic 1D materials (0.34nm), which is reflected by the position of the (002) peak. The lattice spacing of 0.350nm corresponds to a diffraction peak at 26.1°, while the reduced lattice spacing will cause the diffraction peak to shift to higher angles. Fitting the F1DM (002) peak by two different Lorentzian functions shows that both 1D materials and turbostratic graphene are present in the sample, while the single peak in the control sample corresponds only to turbostratic graphene. It is also known that the position of the (002) peak depends on the diameter of the carbon nanotube or nanofiber and that the (002) peak can be fitted by multiple subpeaks [Singh 2010].

[0183] In addition, as observed for large diameter carbon nanotubes, an enhanced (101) peak at 45.3° was observed in F1DM but not in the catalyst-free control ( Figure 2F , the curves for the control (no catalyst) and F1DM are 251-252, respectively. [Singh 2010]

[0184] X-ray photoelectron spectroscopy (XPS) was used to probe the elemental content and incorporation of F1DM (Figure S10a). During the FJH process, the high-boiling carbon content of the plastic was enriched to 97.8% of the graphitic product. High-resolution spectra of the C1s transitions indicated minimal oxygen content and a π-π* transition located at 291 eV. The D parameter of the starting material polymer was 12.8 eV, which increased to 20.2 eV after FJH, indicating that the transition from sp 3 - to sp 2 Thermogravimetric analysis of F1DM under air atmosphere showed a high degradation onset temperature of 630 °C, confirming the largely graphitic nature.

[0185] The detection limit of XPS survey scans is typically 0.5 to 1.0 at%. Therefore, at the concentrations determined by ICP-MS (maximum 0.3 wt%), it is not expected that any signal will be detected by XPS survey scans. In addition, the penetration depth of XPS detection is only 1-2 nanometers. Since TEM imaging shows that iron is present in the nanoparticles under many graphitic carbon layers, it is also possible that no photoelectrons of iron were detected.

[0186] In contrast, iron was dissolved after sample digestion as it was prepared for ICP-MS testing, and ICP-MS has a much lower detection limit. Inductively coupled plasma mass spectrometry revealed the presence of iron in virgin high-density polyethylene (HDPE) feedstock using 0.1 g mL -1 The F1DM formed by the surface wetting method of FeCl3 showed only 0.3 wt% Fe content in the starting material, which was reduced to 0.06 wt% during the FJH process. The reduction in catalyst content during the FJH process may be attributed to the sublimation and degassing of metal ions at high temperatures. [Deng 2021]. Washing with 1M HCl can further reduce the catalyst content to <10 ppm.

[0187] F1DM from unprocessed post-consumer mixed plastics

[0188] 27 million tons of mixed waste plastics go to landfill every year. Convert mixed post-consumer waste plastics into F1DM through grinding, surface wetting and FJH. Figures 3A-3F It was shown that mixed waste plastics consisting of HDPE, low-density polyethylene (LDPE), polypropylene (PP), polystyrene (PS), and polyethylene terephthalate (PET) can be easily upcycled into F1DM by a 3-second-long FJH pulse. Figure 3A is a Raman spectrum (curve 301) showing that F1DM derived from mixed waste plastics is characterized by a large area Raman average spectrum, and the inset (curve 302) shows the radial breathing mode. Figure 3B It is a comparison of the powder XRD of waste plastic (curve 311) and synthetic F1DM (curve 312). Figure 3C is investigated and high resolution XPS (Figs. 321-322). Figure 3D-3F is a SEM image showing the morphology of F1DM derived from waste plastic.

[0189] Other recent studies describe the synthesis of graphitic 1D materials from waste plastics. [Williams 2021; Wang 2022; Jie 2020]. However, these methods typically rely on a two-stage 2h-long pyrolysis followed by a catalyst-assisted chemical vapor deposition process and have not been shown to accommodate mixed waste plastic streams and can produce mixtures consisting of ~30 wt% amorphous carbon or large excess catalysts that must be further removed. [Tripathi 2017; Wu 2016].

[0190] The mixed waste plastic mixture used consisted of 42% HDPE, 20% PP, 20% LDPE, 10% PS, 8% PET, replicating the overall waste plastic composition. It is known that pyrolysis and FJH or PET result in lower carbon yields and lower yields of 1-D graphitic materials. [Algozeeb 202; Yao 2022]. The conversion of polystyrene was further investigated as some studies have reported that aromatic structures result in thicker CNTs. [Yao 2022]. This trend was also observed for F1DM. For F1DM from waste ( Figure 3A ) radial breathing pattern can be observed, and powder XRD ( Figure 3B ) and TGA to determine the complete conversion of waste plastics to graphite structure. Figure 3B An enhanced (101) peak can also be observed in the MgCl2O3 samples, confirming the presence of abundant F1DM from mixed waste plastics.

[0191] XPS can further investigate the high elemental purity in the produced F1DM ( Figure 3C , which shows a 2% increase in oxygen content compared to HDPE-derived F1DM, despite the inclusion of PET, which has 25% oxygen by weight. Additives such as colorants, plasticizers, adhesives or residual waste from the main uses of plastics are considered impurities.

[0192] TGA and XRD of mixed waste plastics ( Figure 3B ) show no significant metallic impurities, as indicated by low residual TGA mass and minimal unidentified XRD peaks. Atomic carbon in these impurities can be converted to graphene, while heteroatoms such as oxygen, metals or halides are sublimed out. F1DM morphologies, including hybrid morphologies, can be observed by SEM imaging, such as Figure 3D-3F shown.

[0193] It has been demonstrated that particle size of the waste polymer feedstock affects the results of FJH [Algozeeb2020], and that finer particle size will allow for more catalyst loading and higher surface area for high-resistance bonding, thereby improving the yield of F1DM. Therefore, the yield of F1DM in post-consumer polymer samples can be further improved by improved grinding. Mixed waste plastics are ground as fine as the hammer mill used allows, but industrial scaling can provide smaller particles and therefore more surface for F1DM formation.

[0194] There are many types of polymers, and the high melting temperatures of some polymers may not allow the introduction of catalysts via melt mixing. To demonstrate the generality of the approach, polyurethanes—thermosetting polymers—were converted to F1DMs via a simple surface wetting technique. These F1DMs synthesized from waste polyurethanes exhibited similar properties and morphologies to those derived from virgin HDPE. The polyurethane-derived F1DMs did have a slight increase in oxygen (2.3%) and nitrogen (1.4%) content, indicating that heteroatom-doped 1D and hybrid morphologies can be formed via FJH, which has been demonstrated for FJH graphene. [Chen 2022].

[0195] Controllable hybridization and F1DM morphology

[0196] 1D and 2D hybrid materials, such as rebar graphene, are desirable for applications due to their exceptional mechanical and electronic properties. [Vedhanarayanan 2018; Yan 2014]. However, these materials are almost exclusively synthesized via multi-step chemical vapor deposition methods that are costly and low-yielding. [Xia 2017; Zhao 2012]. FJH produces 2D graphene morphology, domains of F1DM morphology, and commonly observable regions of colocalization and coalescence of 1D and 2D morphologies. Figures 4A-4I .

[0197] SEM imaging showed that the F1DM was decorated with 2D graphene sheets at its ends, while the 1D morphology occasionally extended all the way through the 2D graphene ( Figure 4A and 4C -4D). The area of ​​the sample ( Figure 4B ) also showed the coalescence of 1D morphologies into networks of larger diameter 1D materials followed by 2D graphitic morphologies. TEM imaging ( Figure 4E-4I ) shows the co-localization of F1DM and graphene. Figure 4F yes Figure 4E High-resolution TEM image of highlighted area 441 in FIG. Circular area 442 highlights the lattice fringes between the bamboo-like carbon nanofibers and the graphene sheets, indicating that they are part of the same lattice. Figure 4H for Figure 4GAtomic resolution bright field TEM image of region 461 highlighted in FIG, showing the hexagonal arrangement of carbon atoms in the uninterrupted graphene sheet at the junction between 1D and 2D morphologies.

[0198] High-resolution imaging ( Figure 4E-4G ) showed that the lattice fringes and edges are uninterrupted from the outer wall of the nanofibers to the larger graphene sheets, indicating van der Waals interactions linking the 1D and 2D domains together. Atomic-resolution TEM imaging ( Figure 4H ) reveals the hexagonal sp 2 Hybrid graphene sheets that are uninterrupted along the edges of the junction between 1D and 2D morphologies indicate covalently linked hybrid materials. Fast Fourier Transform ( Fig. 4I ) indicates AB-stacked graphene, indicating that the hybrid material can show a reduced lattice spacing by XRD and an M peak in Raman spectroscopy analysis ( Figures 2A-2F ).

[0199] FJH parameters, including discharge voltage, catalyst type, loading, and capacitance density, can affect product morphology. Capacitance density is defined in this article as the system capacitance per unit reaction mass. [Beckham 2022]. SEM analysis revealed that catalyst loading and type affect the diameter of the produced F1DM ( Figure 5A-5B ), decreasing catalyst loading resulted in thinner 1D materials being produced, with Fe(III) producing the thinnest F1DMs and Co(II) producing the thickest.

[0200] It is well known that the catalyst type can have a significant effect on the size of the produced CNTs, as different metals have different catalytic graphitization rates and carbon solubility. [Yuan 2008; Thambiliyagodage 2018; Hunter 2022]. In agreement with this paper, many literature reports suggest that iron is more effective than cobalt and nickel due to these effects. FJH parameters such as capacitance density and pulse voltage are directly related to the capacitance current of Eq (1) and affect the diameter of the F1DM ( Figure 5C-5D ), where I, C, V, and t correspond to current, capacitance, voltage, and time, respectively.

[0201]

[0202] Interestingly, capacitive and pulse voltage discharges lead to opposite trends in the F1DM diameter, even though both contribute additional charge to the reaction. However, the discharge rate of a capacitor is not uniform, so doubling the capacitance will not double the current, but will double the discharge time. The amount of time required to discharge a capacitor can be determined by using Eq(2), where R represents the resistance.

[0203] t=C*R*log(V) (2)

[0204] The increased peak discharge voltage allows an increased instantaneous current to discharge through the sample, resulting in higher total power and heating rates. The non-monotonic correlation of capacitance density and discharge voltage with diameter was unexpected but appears to indicate a shift in mechanism. This has been observed previously in partial dependence analyses of machine learning-guided FJH studies, which found that increasing current density leads to a shift from reaction-limited to diffusion-controlled kinetics. [Stanford 2020; Beckham 2022]. Such changes in growth kinetics are common in crystalline materials and are also observed here. [Carroll 2018; Viswanatha 2007]. Representative SEM images of F1DM as each parameter differ suggest that F1DM formation is parameter-sensitive, allowing control over product morphology.

[0205] Qualitative analysis also showed that catalyst type, loading, capacitance density, and discharge voltage can be used to control the morphology and composition of F1DM ( Figure 5E-5H ). The use of Ni(II) resulted in the highest share of 2D material, while Co(II) produced the most hybrid material. The amount of hybrid and 1D morphology produced also decreased as the catalyst loading decreased, which may be attributed to the lower density of catalytic sites for active carbon deposition ( Fig. 5F ). As the power input to the system increases, either by applied voltage or capacitance density, the amount of 1D and hybrid material increases. The diameter of the F1DM product is positively correlated with the amount of hybrid morphology present. The optimized reaction parameters yielded 68% 1D / hybrid morphology ( Fig.5I ). Repeated mixing or sieving further increases the F1DM yield to 90%.

[0206] When the catalyst is loaded on or in the plastic and the conductive CB reaches a lower temperature, it is believed that only the polymer raw material forms the F1DM morphology, while the conductive additive forms the 2D morphology. Conductive additives may be necessary for the FJH process to reduce the resistance of the sample and allow high power discharge. In order to increase the yield of the 1D morphology, repeated mixing can be used, in which the F1DM product (50 / 50 of 1D and 2D morphologies) is used as a conductive additive in the second FJH reaction, increasing the 1D share to ~75% without quality degradation. The use of larger particle conductive additives, such as metallurgical coke, allows the use of simple screening to separate small F1DM products from large particle conductive additives. Screening or repeated mixing allows the production of F1DM consisting of 80-90% 1D and hybrid morphologies without the use of solvent-based or centrifugal separation methods.

[0207] F1DM formation mechanism

[0208] The catalyst-loaded conductive additive does not lead to the formation of F1DM, but rather a 2D graphene morphology surface decorated with metal nanoparticles. High resistance junctions imparted by the plastic feedstock and decomposition of volatiles may be necessary for the formation of F1DM. It is believed that these junctions form hot spots that promote the nucleation of F1DM. To further analyze this effect, uniform samples with similar total resistance and density were tested and evaluated. The ash produced by industrial pyrolysis of plastic waste has a resistance of 7Ω similar to the F1DM feedstock with carbon added, but is uniform. Metal salts were introduced into the pyrolysis ash using surface wetting, and the samples were subjected to FJH using the same parameters used to form F1DM. No 1D morphology was observed by SEM and TEM imaging, indicating that the resistive junctions at the plastic surface require the formation of 1D morphology.

[0209] To further probe whether the resistive junction is the mechanical cause of F1DM formation, the process was repeated using sand (silicon dioxide) instead of plastic. All parameters remained the same, including surface wetting of the sand to introduce the catalyst, mixing with the carbon black conductive additive, and the FJH setup. The samples were ground and sieved after FJH to remove residual inert silica. The results showed graphitization of the carbon black, as well as a small amount of SiC formation, with <20 area % of the carbon converted to F1DM and the remainder converted to 2D graphene morphology.

[0210] This test suggests that the resistive junction may be necessary for the formation of FIDM, but also suggests that the carbon from the plastic may be important for large quantities of FIDM to be produced. Recent work has shown that carbonization in the presence of carbon black or other conductive amorphous carbons can lead to the metal-catalyst-free formation of turbostratic carbon nanoparticles. [Jia 2022]. Amorphous carbon can be converted to graphene sheets as a minor byproduct in the formation of CNTs. [Gog 2013]. This further supports the observation that 2D graphene sheets are produced from carbon black.

[0211] TEM images show the presence of metallic nanoparticles at the base of the plastic-derived F1DM. The lattice spacing matches that of the metal oxide of the original catalyst used, indicating that during the FJH process, the high temperature causes the metal salt to degrade to form nanoparticles that promote the deposition of mobile carbon, which then nucleates to form thermodynamically favorable graphitic domains that extend into the F1DM. At lower catalyst loading concentrations, fewer or smaller nanoparticles will be formed, and a 2D graphene morphology will be formed, explaining why the F1DM morphology and diameter vary with catalyst concentration.

[0212] Similarly, the type of salt catalyst will determine the degradation temperature (catalytic nanoparticles will be formed at this temperature) and the rate of nanoparticle formation, affecting F1DM formation. It is known that both metal nanoparticles and metal oxide nanoparticles catalyze the growth of CNF and CNT materials, so it is not known whether the nanoparticles formed in situ during the FJH reaction are metals or metal oxides. It is believed that the catalytically active species are neutral metal species, which are subsequently converted to oxides once the sample is removed from the FJH reactor and exposed to air. Since the metal or metal oxide catalyst nanoparticles are formed in situ during the FJH reaction, there is no need to add expensive catalysts, such as precious metal nanoparticles, to the reaction scheme, which are commonly used in CVD methods.

[0213] To better understand the relationship between catalyst concentration and F1DM diameter, TEM imaging was used to probe the size of the catalytic nanoparticles when the catalyst concentration was varied. These showed that the size of the catalytic nanoparticles decreased when the catalyst loading concentration was reduced, which resulted in a decrease in the F1DM diameter. At high metal salt loadings, some catalytic nanoparticles could be seen without a surrounding F1DM coating. This suggests that the catalyst concentration in the wetting solution controls the size and abundance of the nanoparticles formed.

[0214] The catalytic role of Fe, Ni, and Co particles in the synthesis of carbon 1D structures is generally considered under CVD conditions, where carbonaceous feedstock is deposited on the surface of the nanoparticles, diffuses through the particles, and incorporates into the growing graphitic domains. [Fouquet 2012]. Most previous studies have focused on the formation of carbon nanotubes from gaseous sources, leaving the catalytic graphitization of amorphous carbon unstudied. [Wang 2007]. Previous work has demonstrated that early stopping of the FJH reaction leads to carbonization products with considerable amorphous content and considerable graphitic lattice disorder, indicating an amorphous intermediate between the polymer and the graphitic product. [Algozeeb 2020]. Furthermore, since a mixture of morphologies is obtained, rather than just 1D morphologies as is typically obtained from catalytic pyrolysis of plastics, this suggests that a different mechanism may be occurring. The solid amorphous intermediate can be converted into a graphitic product, which is 1D when on the catalytic nanoparticles.

[0215] To investigate the effect of metal inclusions within the FJH device, molecular dynamics was used to examine the behavior of the amorphous carbon regions in contact with the Ni nanoparticles ( Fig. 6A ). Fig. 6AThe configuration after the initial pre-annealing is shown, showing some carbon atoms of the amorphous carbon 602 dissolved within the Ni nanoparticles 601. The system is heated and held at 3000K for 4 nsec to simulate the high temperature of FJH. The amorphous carbon undergoes thermal and catalytic graphitization, both of which are accelerated by the high FJH temperature. Catalytic graphitization involves dissolving carbon atoms from amorphous and partially graphitized domains into the Ni particles, which are then deposited on the surface to form large 1D or hybrid graphitic domains ( Figure 6B ). Figure 6B The final structure is shown, which shows that carbon fibers begin to form through carbon interactions and catalytic graphitization, as shown by arrows 613.

[0216] The large size of the catalytic nanoparticles (450 Ni atoms) resulted in a large diameter carbon product that was different from the existing literature results. [Chiang 2009]. Analysis of the graphitization rate determined that the catalytic process accelerated the conversion of amorphous carbon ( Figure 6C-6D ), and the curvature and size of metal nanoparticles are conducive to the formation of 1D and hybrid morphologies. Figure 6C The graphitization levels of all carbon and carbon affected by Ni are shown (the curves for affected Ni and total Ni are 621 and 622, respectively), indicating the catalytic effect of Ni atoms on the graphitization of affected carbon atoms. Fig.6D The percentage of carbon affected by the Ni particles throughout the simulation is shown, demonstrating the interaction of the mobile carbon with the Ni catalyst even on the short simulation time scale.

[0217] Uses of Nanocomposites

[0218] Both 1D and 2D graphite morphologies can be used in composites due to high tensile strength, thermal and electrical conductivity, and low density. Hybrid materials can yield excellent mechanical properties due to the 2D morphology increasing the interfacial adhesion between the nanomaterial and the matrix.

[0219] F1DM was highly dispersed in 1% Pluronic surfactant aqueous medium to obtain 1.63 mg mL -1 Different amounts of ground F1DM powder were weighed into centrifuge tubes and solvent was added to give an initial loading concentration (~1 mg F1DM powder mL -1 Solvent). The centrifuge tube was then sonicated in a cup-horn sonicator for 10 minutes (Cole-Parmer Qsonica 448) and centrifuged at 550 relative centrifugal force for 5 minutes to remove larger aggregates. After centrifugation, the supernatant was decanted and diluted 100 times because the graphene concentration resulted in very high absorbance. The absorbance of the solution was measured at 660 nm. An extinction coefficient of 66 L g was used. -1 cm -1 Beer's law was used to determine the concentration.

[0220] 7g of F1DM was prepared to test 0.5, 2 and 5 wt% loadings. F1DM was easily dispersed in the vinyl ester matrix material by a brief cup-shaped horn type ultrasonic treatment. Vinyl ester (VE) resin was obtained from Fiberglass Supply Depot and used as it was. Methyl ethyl ketone peroxide (MEKP) was obtained from Fiberglass Supply Depot and used as a catalyst / hardener for the resin as it was. The F1DM / VE composite was prepared by combining 5.0g of vinyl ester and 20-200mg of F1DM (depending on the required loading) in a 20mL flash tube. Then, a magnetic stirring bar was used to mix the solution at 300rpm for 30 minutes. After stirring, the mixed solution was sheared at ~10,000rpm for 5 minutes using a homogenizer (Tissue Tearror 986370-07 homogenizer; 120VAC, 1.2A) from Cole-Parmer. Five drops (-0.15 g) of MEKP were then added to the solution while stirring with a magnetic stir bar at 300 rpm for 5 minutes. The solution was then poured into a release-coated PDMS mold and allowed to cure overnight.

[0221] The F1DM reinforced vinyl ester resin nanocomposites tested using nanoindentation demonstrated a dramatic increase in compression modulus even at 0.5 wt%, resulting in a 21% increase. Macroscale mechanical testing showed that the F1DM composites exhibited significant increases in both tensile elongation and compression ( Figure 7A-7B ) with tensile strength increased by 92%, 130% and 48% and toughness increased by 174%, 304% and 63% at 0.5, 2 and 5 wt%, respectively.

[0222] The decrease in mechanical properties when the loading increases from 2% to 5% is thought to be a result of F1DM aggregation in the vinyl ester matrix material. It is well known that nanocomposites do not show a linear increase in mechanical properties when more reinforcement is added, but rather have an optimal maximum, typically less than 5% loading. [Medupin 2019; Roy 2018]. The interfacial properties of polymer nanocomposites are complex and directly affect the mechanical properties at the macroscale, but can depend on the surface area, aspect ratio and dispersion of the nanomaterial, the viscosity of the matrix material, and the interfacial interactions between the phases. [Ashraf 2018; Zare 2016].

[0223] The properties of F1DM-loaded vinyl esters were compared with those of vinyl esters loaded with commercially available carbon nanotubes prepared using conventional methods ( Fig. 7A ). F1DM outperforms commercial nanotubes in nanoindentation and macro compression tests ( Fig. 7A), which may be attributed to the hybrid morphology and high graphite purity, and F1DM improves the properties of pure vinyl ester matrix materials ( Figure 7B ).

[0224] To show the advantages of F1DM compared to graphene produced by FJH without the inclusion of a catalyst, the best performing sample (5% F1DM) was compared to a similarly prepared sample containing 5% 2D graphene produced by FJH. Figures 8A-8G and Figures 9A-9D It is shown that F1DM outperforms graphene produced by flash Joule heating in nanoindentation tests. Figures 8A-8C shows the nanoscale compression test, Figures 8D-8E shows a macro-scale compression test, Figure 8F-8G A macroscale tensile test is shown. Fig. 9A (The curves for Blank, 0.5% F1DM, 2% F1DM, 5% F1DM and 5% CT are 901-905 respectively) Nanoscale compression testing is shown. Fig. 9B (Multiple curves, pure VE, cheap tube with 0.5% VE, F1DM with 0.5% VE are 911-913 respectively) and Fig. 9C (Multiple curves, curves 921-923 for pure VE, cheap tube with 2% VE, and F1DM with 2% VE respectively) show the compression test at macro scale. Fig.9D (Multiple curves, curves for 0% F1DM in VE, 0.5% F1DM in VE, 2% F1DM in VE, and 5% F1DM in VE are 931-934, respectively) show tensile testing at a macro scale.

[0225] F1DM outperforms graphene produced by flash Joule heating in nanoindentation tests, which may be attributed to the improved matrix penetration and strain propagation properties of vinyl esters due to the hybrid morphology of F1DM. Therefore, it is shown that as an additive in vinyl esters, the hybrid morphology of F1DM is mechanically superior to 1-D and 2D graphitic carbon nanomaterials.

[0226] 1D graphite nanomaterials are well known for their electrical conductivity, and this property is often exploited in nanocomposites. Thus, the conductivity of the produced F1DM / vinyl ester was measured as shown in Table 1, which shows that the conductivity increases with increasing load; however, commercial MWCNTs are superior to F1DM as a conductive additive. This may be a result of the longer aspect ratio of commercial MWCNTs compared to F1DM.

[0227] Table I

[0228] Conductivity Measurements of Nanomaterial-Enhanced Vinyl Ester Composites

[0229]

[0230]

[0231] Cradle-to-gate life cycle assessment

[0232] A cradle-to-gate life cycle assessment was performed to examine the FJH approach to F1DM synthesis, as the impact of application and handling will vary negligibly based on the synthesis method of the graphite 1D material.

[0233] With respect to LCA scope, objectives, functional units, and inventories, a cradle-to-gate LCA is a systematic analysis of the demands and impacts associated with a product, from the raw materials required for synthesis to the handling and manufacture of the product, and does not examine the final disposal target use application or disposal of the product. The specific objective of the LCA in this paper is to assess the demands and environmental impacts caused by the FJH production of F1DM to compare with a literature benchmark that studies the production of graphite 1D materials synthesized using other methods. The system considered here includes three main steps: feedstock preparation, reaction feedstock preparation, and FJH reaction. The transportation of raw materials is not considered here, and a laboratory-scale approach is assumed. The functional unit considered here is 1 kg of high-purity graphite 1D material powder with >95% graphite content, as this is the purity level typically sold for gram-scale or larger applications such as composites or coatings. Environmental impacts associated with the production of waste polyethylene are not considered here; however, the burden of collecting and separating post-consumer waste polyethylene has been included. [Martin-Lara 2022]. The direct energy input of the FJH process was measured experimentally, and the cumulative demands and impacts were calculated using the Argonne National Laboratory GREET life cycle assessment.

[0234] The surface wetting method uses the original HDPE powder, wetted with 4L of 80 / 20vv water / EtOH solution per kg of polymer, bath sonicated for 15 minutes, and centrifuged to recover 75% of the solution. The polymer mixture is air dried and 20% by weight of carbon black is mixed using ball milling. The mixture of salt-loaded polymer and conductive additive is then subjected to FJH and used without further purification to obtain 1kg of F1DM mixed form with carbon and graphite content>95%. Alternatively, the melt mixing method considers waste polyethylene with 0.25% by weight of acetylacetonate iron loaded. The uniform molten mixture is cooled and hammer ground to 1mm particle size, and then mixed with 33% by weight metallurgical coke (3mm particle size) to obtain a conductive mixture. The mixture is then subjected to FJH, pushed out of a quartz tube, and sieved to separate F1DM from metallurgical coke to obtain a high-purity 1D form with>95% carbon and graphite content. A direct comparison of our life cycle assessments with other literature values ​​would be possible if all used databases (e.g. GREET, SimaPro, Ecoinvent and Gabi) followed ISO Best Practices procedures.

[0235] A general scheme for the industrial synthesis and life cycle inventory of nanotubes is shown in Figures 10A-10C . Fig. 10A A flow chart showing a general business process, Fig. 10B A flow chart showing melt mixing of F1DM and FJH, and Fig. 10C Flowchart showing surface wetting of F1DM and FJH. This life cycle assessment considered two different synthesis scenarios: melt mixing of waste polymers and surface wetting of virgin polymers to determine the cumulative energy demand, overall warming potential and cumulative water use ( Figure 7C-7E ).

[0236] F1DM synthesis is compared to FJH 2D graphene synthesis from post-consumer waste plastics, where no catalyst loading is required. [Wyss II 2022]. F1DM synthesis using surface wetting consumes 683 MJ and 185 L of water and produces 27 kg CO2 equivalent per kg of graphite product produced. Most of the impact comes from the original polymer and the conductive additive. When the melt mixing scenario is considered, the method uses 395 MJ and 111 L of water while producing 26 kg CO2 equivalent per kg of graphite product produced. The impact arising from the synthesis of waste polyethylene is ignored, but the collection and separation burden is considered. For the scenario of melt mixing of waste polymers, most of the burden comes from FJH.

[0237] Comparison of the FJH synthesis of graphite 1D and hybrid materials with the literature is complicated by the wide diversity of morphologies produced. Single-walled nanotubes are not considered comparable products; only multi-walled nanotubes or nanofibers have been compared. Comparison of the FJH synthesis of F1DM with an ISO-compliant life cycle assessment of graphite 1D materials demonstrates a reduction in energy use and overall warming potential for the synthesis of 1 kg of graphite 1D material. Figure 7F A comparison of the two FJH syntheses of F1DM strategies considered in the life cycle assessment with literature life cycle assessments probing carbon nanotube or nanofiber synthesis is shown. Table II provides Figure 7F The values ​​and references of the data plotted in Figure 7 compare the cumulative energy demand (CED) and global warming potential (GWP) of the F1DM strategy (which is within the oval 701) with literature life cycle assessments (LCAs) that probe the synthesis of MWCNTs and CNFs (which is within the box 702). The units of CED are MJ kg -1 , and the unit of GWP is gCO2 eq kg -1 product.

[0238] Table II

[0239]

[0240] The literature average for the cradle-to-gate energy requirement to form 1 kg of graphite 1D material is 4,855 MJ, while the average overall warming potential is 355 kg CO2-eq, representing an 86-92% reduction in cumulative energy demand and a 92-94% reduction in overall warming potential over the FJH route.

[0241] Further applicability

[0242] FJH can rapidly and controllably synthesize a variety of high-value graphitic 1D or hybrid materials with proven value in a cheap, sustainable and efficient manner using simple earth-abundant salts and waste plastics. In addition, F1DM can be doped or functionalized.

[0243] Synthesis of Boron Nitride Nanotubes (BNNTs) by FJH

[0244] In an embodiment, the present invention also relates to the synthesis of BNNTs by using a flash Joule heating (FJH) method. The method is carried out in the solid phase and at a moderate reaction pressure (1atm Ar) and temperature (~1800K), and no solvent is used. Ammonia borane (AB) and bis(acetylacetonate) nickel (II) (Ni(acac)2) can be used as precursors and catalysts, respectively. After synthesis, the products (mainly BNNTs and h-BN) can be directly separated from the conductive additive.

[0245] Boron nitride nanotubes (BNNTs), known as structural analogs of carbon nanotubes (CNTs), have attracted great attention due to their superior intrinsic properties and wide range of applications. Despite their potential, it remains challenging to rapidly synthesize BNNTs with high yield and quality, which limits the development of their practical applications. Using an all-solid-state catalytic flash Joule heating method (catalytic growth process), BNNTs can be synthesized within 1 second to obtain BNNTs and BN nanosheets with high yield and high selectivity. The product can be directly separated from conductive additives such as carbon or metal powders. This further provides a continuous and scalable method for the synthesis of BNNTs using the FJH method, and provides potential catalytic synthesis of other materials.

[0246] f-BCN with various chemical compositions and turbostratic features were synthesized from BH3NH3 and carbon black in <1 s using an ultrafast solvent-free FJH method. The atomic percentage of carbon can be controlled from ∼0% to ∼100%, and spectral analysis shows that the VBM can be tuned accordingly. At lower carbon percentages, f-BN closely approaches t-BN in its spectral properties. Calculations support the existence of a turbostratic structure and an energy barrier that hinders the conversion to a well-aligned counterpart. The resulting f-BCN layers with disordered orientation are easily detached. Stable dispersibility of f-BCN samples in aqueous Pluronic (F-127, 1 wt% in deionized water) is demonstrated in comparison with commercial h-BN nanosheets.

[0247] Furthermore, the addition of f-BCN as barrier filler in PVA nanocomposites showed better compatibility and they imparted higher corrosion protection efficiency. The turbostratic morphology of f-BCN is difficult to reproduce by common bottom-up methods such as CVD and hydrothermal methods, whose cooling rates are 100-1000× lower than that of FJH. The FJH method provides a high-yield process for the synthesis of large quantities of turbostratic materials.

[0248] FJH synthesis of BNNT

[0249] For the synthesis of BNNTs by FJH, ammonia borane (AB) was chosen as a representative precursor because its decomposition at different temperatures has been studied and both B and N are provided in stoichiometric ratios. AB has been extensively studied as a monolayer h-BN precursor in CVD. [Tay 2014; Stehle 2015; Koepke 2016]. Suib et al. demonstrated that the decomposition of AB produces semi-crystalline h-BN. [Frueh 2011] Prior to h-BN growth, it is common practice to perform a low-temperature decomposition of AB to produce polymeric radical species and cycloborazine, which are more reactive in CVD. The BN bonds are maintained during the decomposition, while H2 undergoes a gradual loss. The FJH system (and parameters) that can be used can be based on the system described and described in the Tour'642 application and the Tour'111 PCT application, with modifications as described below. [See also Luong 2020; Chen 2022; Deng 2022].

[0250] In an embodiment of the present invention, Figures 11A-11B The apparatus diagram and temperature curve are shown in . In a typical FJH process, a mixture of AB, Fe(acac)3 / Ni(acac)2 catalyst and metallurgical coke (metallurgical coke) is compressed in a quartz tube between two graphite rods. The two graphite electrodes are connected to a capacitor bank with a total capacitance of 60mF. Then, the current through the sample is measured after rapid discharge at different voltages. The real-time temperature can be measured using an infrared sensor, as plotted ( Fig. 11B ). The heating rate is up to 5×10 3 K / s. To reduce the carbon content of the product, metallurgical coke (12-20 mesh, or 840-1680 μm) is used instead of carbon black powder as a conductive additive. The large particle size of metallurgical coke allows for easy separation by screening, and the weight loss of metallurgical coke at the reaction temperature is negligible. AB and its decomposition products are easily oxidized at high temperatures. To reduce oxygen contamination, O-ring seals are used on both electrodes of the quartz tube, and Ar is used as a protective atmosphere. Mix AB and Ni(acac)2 and heat to 110°C to ensure uniform molten mixing ( Fig. 11C ). Two types of tubes can be used in the FJH process ( Figures 11D-11E ).

[0251] For example, in a typical experiment, ammonia borane is mixed and ground with 3 wt% Ni(acac)2 and 3 wt% Fe(acac)3, and heated to 120°C for 10 minutes. The mixture is then mixed with metallurgical coke in a mass ratio of 1:1. The reactants are added to a quartz tube (8 mm inner diameter, 12 mm outer diameter). Graphite rods are used as electrodes on both sides of the quartz tube, and copper wool is used between the graphite rods and the electrodes. The tube is sealed with two O-rings and loaded into a fixture. During the FJH reaction, Ar gas (≈1 atm) is used as an inert gas to avoid oxidation of the sample. A capacitor bank with a total capacitance of 60 mF is charged by a DC power supply. The discharge time is controlled by an Arduino controller relay with a programmable millisecond delay time. The optimal conditions for BNNT synthesis are twice 90V 500ms. After the FJH reaction, the equipment is ventilated and cooled to room temperature. The flashed product was screened through a 40 mesh screen (425 μm metric) to separate metallurgical coke and BNNT / BN products. The mass yield was ~45% of the theoretical yield of BN in the quartz tube and ~60% in the PEEK tube. ~30% of the product was tubular structure and the rest was flake structure.

[0252] Characterization of BNNTs

[0253] Spectroscopic analysis and imaging techniques were used to confirm the formation of BNNTs in the flash products. Figures 12A-12D In the FTIR spectrum, the flash product has a peak at 1317 cm -1 The BN stretching peak is at 780 cm -1 The BNB bending peak is shown at . Fig. 12A (The curves for the AB precursor and the flash product are 1201-1202, respectively.) These peaks are consistent with those in commercial h-BN. Some peaks are consistent with those of the AB precursor, indicating the presence of a small amount of AB.

[0254] There is no Raman peak of AB precursor in the flash product. Fig. 12B (The curves of AB precursor and flash product are 1211-1212 respectively). -1 Feature E appears 2g peak, which is lower than the E 2g Peak (~1368cm -1 ). The blue shift can be attributed to the strain in the tubular structure and E 2g The hardening of patterns. [Arenal 2006].

[0255] In the XRD pattern, the AB precursor peak in the product disappeared. Fig. 12C(The curves for the AB precursor and flash product are 1221-1222, respectively). In curve 1222, the peak at 26.0° corresponds to the characteristic (002) diffraction peak of BN, and the peaks at 43.4° and 44.5° correspond to the (100) and (001) diffraction peaks. The broadened peaks indicate that the formed BN sheets and BNNTs are not highly crystallized. BNNTs also show a broadened (002) peak compared to previously reported h-BN materials. [Lee J 2021; Kim H 2021].

[0256] The purity of the BN product was confirmed by the B 1s spectrum. Fig.12D (The curves for the AB precursor and the flash product are 1231-1232, respectively). Slight oxidation (~10%) can be observed in the AB precursor due to the rapid absorption of water by AB in the air. In the flash product, only BN bonds are present, with no obvious BO and BC bond formation. The B / N ratio is ~1.06.

[0257] The formed BNNT structure can be seen in the SEM image. Figures 13A-13I . Can be in quartz tube ( Figures 13A-13C ) and PEEK tubes ( Figures 13D-13F ), revealing that tube growth is independent of an external container. Multi-walled BNNTs showed hollow and non-hollow morphologies in the sample. However, the tubular structures formed in PEEK exhibited a higher hollow fraction, which may be due to the higher pressure that can be maintained in the PEEK tube. High pressure promotes the selectivity of BNNTs to BN sheets and BNNT crystallinity. [Bae 2022]. The length and diameter of BNNTs are 20-50μm and 50-100nm, respectively. The selectivity observed in the flash product is ~30%, and the rest of the product is sheet-like BN structure. Figures 13H-13I .

[0258] Two types of BNNT morphology can be distinguished in the TEM images. The tubes without obvious hollow structures show a diameter of 30-50nm, while the hollow tubes show a diameter of 50-100nm. TEM analysis shows crystalline domains on the outer regions of BNNTs. The interlayer spacing of 0.353nm is slightly larger than that of crystalline h-BN (0.333nm). The results are very consistent with the broadening (002) and shifted peaks in the XRD pattern. The increased lattice spacing will cause the diffraction peaks to reach larger angles.

[0259] Also there Figures 14A-14B BN flakes (lateral size ~100 nm) are noted in the figure. Clear edge fringes indicate good crystallinity of the few-layer BN nanosheets. Bright field (BF) and high-angle annular dark field scanning transmission electron microscopy (HAADF-STEM) images, together with elemental mapping, indicate the presence of B and N in BNNTs and BN nanosheets ( Figures 13G-13I), which is consistent with the XPS results.

[0260] The role of catalysts

[0261] The role of catalysts in the FJH technique has been discussed above in the synthesis of 1D carbon materials. The use of appropriate catalysts can promote reaction rate and selectivity. In order to study the role of catalysts in catalytic decomposition and BNNT growth, various types of catalysts were used in the synthesis. No obvious tubular structure formation was observed in the reactions using metal borides, metal chlorides, and metal powders as catalysts, indicating that the catalyst effect may be different from the BNNT growth process in the CVD method.

[0262] It has been found that the combined Ni(acac)2 / Fe(acac)3 catalyst shows enhanced selectivity towards tubular structures compared to flakes. The presence of the Ni / Fe catalyst was confirmed in the elemental mapping of the HAADF-STEM images. Figure 14K At ~400 °C, the main decomposition products of Fe(acac)3 are Fe2O3 / Fe3O4 [Kim H 2021; Toyos-Rodriguez

[0263] Metal oxide particles can be found in the head of BNNT. The growth mode is consistent with the typical VLS mechanism in CVD. The growth mechanism of BNNT in FJH process is considered to be as follows: active BN species are first formed and evaporated during rapid dehydrogenation at over 200 °C, followed by decomposition of Ni(acac)2 / Fe(acac)3 into metal oxide particles at ~400 °C. The final dehydrogenation step from NHBH(s) to BN(s) requires high temperature of over 1200K. [Demirci 2020]. Semicrystalline h-BN was found to form at ~1500K [Frueh 2011], and the h-BN morphology is similar to the BN sheets in our flash product. BNNTs start to grow in the temperature window of 1500-1800K. Rapid dehydrogenation and high local BN species concentration enable selectivity for BNNTs (rather than h-BN). Comparison of FJH synthesized BNNTs with other BNNT synthesis methods is listed in Table III. The FJH method reduces the cost of large-scale production of BNNTs by lowering the reaction temperature, pressure, and duration.

[0264] Table III

[0265] Comparison of recent BNNT synthesis methods

[0266]

[0267]

[0268] Turbostratic boron-carbon-nitrogen (BCN) synthesis via FJH

[0269] In an embodiment, the present invention also relates to the synthesis of BCN with turbostratic structure and high in-plane crystallinity by an all-solid-state flash Joule heating (FJH) system. It provides a short pulse of high electrical energy followed by rapid cooling (10 3 ~10 4 Ks -1 ), all in <1 s. Starting from BH3NH3 and carbon black, the FJH-product is called flash BCN (f-BCN-x, where x is the carbon percentage in the reactants). Other conductive powder additives, such as iron and tungsten, can also be used instead of carbon black.

[0270] By varying the carbon content in the reactants, the atomic percentage of carbon can be controlled from 0% to 100%, as determined by X-ray photoelectron spectroscopy (XPS). At lower carbon percentages, spectral features were observed that were close to those of pure turbostratic h-BN (t-BN).

[0271] The f-BCN has a turbostratic structure, which facilitates its exfoliation by different mechanical methods, such as tape exfoliation, unidirectional mechanical shearing, and bath sonication. The calculation results show the existence of a turbostratic structure and an energy barrier for conversion to a well-aligned counterpart.

[0272] Hexagonal boron nitride (h-BN) and graphene are two common layered materials with an interlayer interaction of ~26 meV atomic -1 (~2.5 kJ mol -1 )[Rydberg 2003], while the in-plane binding energy is ∼450 kJ mol -1 , which is more than two orders of magnitude higher than the interlayer interaction. Therefore, the formation of turbostratic materials with a high degree of in-plane crystallinity can be kinetically controlled by thermal annealing followed by ultrafast cooling. Thermal annealing promotes the formation of an ordered in-plane structure. [2] And the ultrafast cooling process maintains the mismatched stacking sequence in local, rather than global, energy minima. This can also be extended to doped graphene.

[21]

[0273] Compared to commercial h-BN and graphene, f-BCN has better temporal stability when dispersed in aqueous Pluronic (F-127, 1 wt% in deionized water). Polyvinyl alcohol (PVA) nanocomposites containing 10 wt% f-BCN coated on copper foil impart improved corrosion resistance when subjected to 0.5 M sulfuric acid or 3.5 wt% saline solution.

[0274] Synthesis of f-BCN

[0275] Fig.15AAn ultrafast all-solid-state preparation process based on FJH is shown to synthesize f-BCN in <1 s. As discussed previously herein, the FJH system (and parameters) that can be utilized can be based on the system illustrated and described in the Tour '642 application and the Tour '111 PCT application, with modifications as described below.

[0276] In a typical flash process, a mixture of BH3NH3 and commercial carbon black is lightly compressed in a quartz tube between two copper electrodes. BH3NH3 is chosen as the reactant because it acts as both a boron and nitrogen source and there are preformed BN bonds in the precursor. During the reaction, the carbon black acts as both a carbon source and a conductive agent. A capacitor bank in the circuit is used to provide electrical heat energy to the reactants.

[0277] By varying the carbon content in the mixture, f-BCN with various compositions and turbostratic structures can be synthesized using the FJH method. In a typical flash reaction at a voltage of 150 V and a sample resistance of ∼40 Ω, the current through the sample reaches ∼15 A within a discharge time of ∼600 ms. The total amount of electrical energy is 3.1 kJ g -1 , and the energy cost of converting 1 ton of BH3NH3 precursor into flash product is ~$19. The real-time temperature can be measured using an infrared sensor, such as Fig. 15B During the heating phase, the estimated -1 The heating rate is ~600ms, the temperature reaches ~1220K, and then ~1600Ks -1 Cool down quickly.

[0278] Other conductive additives that do not contain carbon, such as tungsten and iron, have also been tried, and the flash products are called f-BN-W and f-BN-Fe, respectively. Specifically, the iron powder can be collected by a magnet and reused. This results in the formation of BN without obvious carbon signals.

[0279] Due to the possible catalytic effect of Cu in the reaction process, graphite spacers were used as a substitute for Cu wool plugs. To facilitate degassing and avoid tube bursting, the diameter of the graphite spacer was 1 mm smaller than that of the quartz tube. BN was prepared using this graphite spacer.

[0280] Previous pyrolysis dehydrogenation analysis has reported that there are three thermal decomposition steps to form BN-based structures from the BH3NH3 precursor [Frueh 2011], and the overall reaction is highly exothermic (-171 kJ mol -1 ). This drives the reaction to completion, even though the third step, dehydrogenation of NHBH(s) to BN(s), has a high kinetic barrier and typically requires relatively high temperatures of 1200–1400 K. [Demirci 2020; Frueh 2011]. The thermochemical equation is shown in Eq. (3),

[0281] BH3NH3(s)=3H2(g)+BN(s) ΔfH θ =-171.1 kJ mol -1 (3)

[0282] There are three stepwise thermal decompositions (shown in Eqs. (4)-(6)) to form BN crystals from the BH3NH3 precursor [Frueh 2011], and the overall reaction is highly exothermic. The third step, dehydrogenation, NHBH(s) to BN(s) in Eq. (6), is the rate-limiting step and typically requires higher temperatures of 1200-1400 K.

[0283] BH3NH3(s)=H2(g)+H2B=NH2(s)(343K-373K) (4)

[0284] H2B=NH2(s)=H2(g)+HBNH(g)(393K-403K) (5)

[0285] HBNH(g)=H2(g)+BN(s)(1200K-1400K) (6)

[0286] Compared with other bottom-up methods such as CVD [Xu D 2018; Tan 2015] and hydrothermal methods [Ding 2021; Ding 2019], which usually involve temperatures of <10 K s -1 The FJH method has a much slower cooling rate and leads to the formation of a well-aligned stacked morphology, while the FJH method has a 100-1000× faster cooling rate and produces Fig. 15C The turbostratic BCN (t-BCN) shown in . The simulations were performed using the finite element method (FEM) and it was found that the temperature reached in most of the samples was sufficient to drive the third decomposition step because the time scale of uniform energy input is relatively short compared to that of thermal diffusion.

[0287] Taking h-BN as an example, a nudged elastic band (NEB) simulation was performed to study its thermodynamic stability against in-plane rotation. Fig.15D (For 1.3×1.3nm 2 , 1.7×1.7nm 2 , 2.0×2.2nm 2 , 2.5×2.6nm 2 、4.3×4.5nm 2 、5.6×5.8nm 2 and 6.8×6.9nm 2, curves 1501-1507 respectively) show the potential energy distribution of h-BN sheets of different sizes along the minimum energy path from AA'- to AB-stacking. All potential energies are normalized by the total number of atoms in the small h-BN sheet and relative to the most stable AA' stacking mode. Calculations show that: (1) The energy of t-BN is generally ∼0.5 kJ mol higher than that of AA'-stacked h-BN -1 When the h-BN sheet is very small, the energy difference can be even greater; (2) except for the smallest h-BN sheet (1.3×1.3nm 2 ), all other energy distributions show an energy barrier for rearrangement from turbostratic (rotation angle ≠ 0° or 60°) stacking to AA' or AB-stacking. This rearrangement barrier is the cause of the metastability of t-BN; (3) For larger h-BN sheets, the slope of the energy distribution close to 0° is steeper. This is because even when the rotation angle is small, larger h-BN sheets have a higher chance of interlayer misalignment (for example, N on top of N or B on top of B, resulting in large electrostatic repulsion). As listed in Table IV, the rearrangement barrier per atom is almost independent of size (~0.054 kJ mol for AA'). -1 = 0.56 eV, and for AB ~ 0.039 kJ mol -1 =0.40 eV). (In other words, the energy barrier for the rearrangement of the entire h-BN sheet is in terms of the total number of atoms, scaled with the sheet area.) Therefore, the formation of BN-based turbostratic structures is kinetically possible, which can be achieved by the FJH method with ultrafast heating and cooling processes.

[0288] Table IV

[0289] Energy barriers for the rearrangement of h-BN sheets of different sizes from turbostratic to AA' or to AB stacking

[0290]

[0291] Spectral analysis and crystal structure of f-BCN

[0292] When a mixture of BH3NH3 and 20 wt% carbon black is used as the reactant, the flash product shows spectral characteristics similar to h-BN. Therefore, f-BCN-20 (or any f-BCNx where x is less than or equal to 20) is also referred to as flash BN (f-BN) in this context. BH3NH3 and f-BN can be analyzed using Fourier transform infrared spectroscopy (FTIR); note that there are no interfering peaks from carbon black or flash graphene (FG) [Luong 2020] in the IR. Fig.16AAs shown in Figure 2, there are no obvious NH or BH stretching bands in the f-BN product (1601-1603 for the curves of BH3NH3, f-BN, and h-BN, respectively), which indicates the complete conversion of BH3NH3 [Frueh 2011]. The f-BN product shows a BN stretching peak in the IR spectrum (E 1u Model, ~1353cm -1 ) and BNB bending peak (A 2u Model, ~782cm -1 )[Zou 2019], which is similar to the spectrum of commercial h-BN. At ~1074 cm -1 The acromion belongs to the BC zone.

[0293] FTIR results and Fig. 16B The Raman spectra of BH3NH3 and f-BN are consistent (1611-1612 respectively). -1 There are many Raman peaks for BH3NH3, which do not exist in f-BN, and characteristic E 2g Compared with most h-BN, the E 2g The peak shows a blue shift as the number of layers decreases, and is due to the shorter BN bonds and E 2g Mode hardening, which exists in isolated monolayer h-BN for ~4 cm -1 Blue shift. [Gorbachev 2011; Cai 2017].

[0294] from Fig. 16C The representative high-resolution Raman spectra shown (curves 1621 and 1622 for f-BN and h-BN, respectively) show that feature E 2g Peak exists ~3cm -1 The blue shift and lower integrated intensity I(E 2g ), which is similar to the characteristics of few-layer h-BN sheets and indicates weak coupling interactions between adjacent layers. [Gorbachev 2011].

[0295] exist Fig.16D The E of 100 different points on f-BN and h-BN was studied. 2g Peak positions (circles 1631-1632 for f-BN and h-BN, respectively). Commercial h-BN belongs to bulk h-BN, and its E 2g The peak is concentrated at 1365.3 cm -1 At, with a narrow distribution (~0.2cm -1 , red shaded area). f-BN has a higher average E 2g Peak (~1368.7cm -1), with a wider distribution (~2.6cm -1 ), and ~72% of the area showed E 2g This indicates the dominant decoupling effect in the f-BN sample.

[0296] Fig.16E The scheme in shows a normal in-plane lattice constant of ∼0.25 nm and an interlayer spacing of ∼0.33 nm in a well-aligned h-BN crystal 1641. In a t-BN crystal 1642 there are random translational and rotational orientations of individual sheets with a larger average interlayer spacing.

[0297] exist Fig.16F The turbostratic nature of the f-BN samples was further investigated by X-ray diffraction (XRD) in

[19] (circles 1651-1652 for f-BN and h-BN, respectively). The (002) diffraction peak becomes broader but less intense and shifts to lower angles, from ~26.7° to 26.1°, indicating an expansion of the interlayer spacing by ~2.3%. The (100) and (101) peaks in f-BN merge into a broad (10) peak, and long-range diffraction peaks such as (110) and (004) are absent. These results support the absence of an ordered structure with basal planes and the presence of a turbostratic structure. [Alkoy 1997; Thomas 1963; Gladkaya 1986].

[0298] Elemental analysis by XPS indicated an atomic ratio of B to N of -1.05 and the presence of 6.7 wt% C, see Table V.

[0299] Table V

[0300] Element contents determined by XPS spectral analysis

[0301] B N O C Commercial h-BN 45.8% 47.5% 5.1% 1.7% f-BN 41.1% 38.9% 13.3% 6.7% <![CDATA[BH3NH3]]> 46.7% 49.0% 4.3% /

[0302] High-resolution B1s and N1s spectra show the dominance of typical BN bonds (~190.5 eV) and NB bonds (~398.2 eV). Figure 16G (The curves of f-BN and h-BN are 1661-1662 respectively); Fig.16H (The curves for f-BN and h-BN are 1671-1672, respectively). [Ba 2017; Hu 2019]. A small BC peak (~187.3 eV) is observed, which is consistent with Fig.16AThe BC band shown in FTIR is consistent. The valence band of f-BN shows a valence band maximum (VBM) of -3.10 eV, which is slightly downshifted compared to the valence band maximum of commercial h-BN (-2.70 eV). This downshift is caused by the introduction of some O and C atoms in f-CN. The UV-vis spectra of commercial h-BN and f-BN show an optical band gap of ~6.0 eV (Figure S10, Supporting Information). [Ba 2017]. Therefore, FJH synthesis can be an effective method to adjust the VBM by introducing heteroatoms.

[0303] The Brunauer–Emmett–Teller (BET) method showed that the specific surface area of ​​f-BN (~143 m 2 g -1 ) is the specific surface area of ​​commercial h-BN (~22m 2 g -1 ). The larger surface area of ​​f-BN may be the result of the platelet size and the average number of layers. The larger nanopore size distribution may come from the gaps between the platelets. On the other hand, commercial h-BN samples consist of thick microplatelets with >10 layers and a well-aligned structure.

[0304] The lateral size of the f-BN sheet can reach ~4.3μm, with a wrinkled structure. High-resolution transmission electron microscopy (HR-TEM) analysis shows two stacked f-BN layers. The corresponding fast Fourier transform (FFT) pattern shows the presence of two sets of six-fold diffraction patterns close to each other, with a rotational mismatch of ~12°, which is caused by the turbostratic structure of f-BN. Fig.16I (Inset 1681 shows the FFT graph, and the scale bar is 5 nm -1 ).

[0305] Polycrystalline materials consist of many crystalline domains with different sizes and orientations, which also give multiple sets of diffraction patterns. For polycrystalline films, in-plane grain boundaries separate the domains in real space, and the film shows multiple sets of diffraction patterns in reciprocal space. Turbostratic materials are solids whose basal planes have unaligned surfaces. Each individual sheet has its own translational and rotational orientation in real space, and it shows a set of diffraction patterns in reciprocal space. Therefore, the diffraction pattern of a polycrystalline film comes from the in-plane domains, while the diffraction pattern of a turbostratic material is caused by the out-of-plane domains (each individual sheet).

[0306] This means that there are several solutions to distinguish polycrystalline and turbostratic materials by TEM, namely

[0307] (1) Each set of diffraction patterns can be inverse Fourier transformed in reciprocal space, and the reconstructed image in real space reflects the relative correlation between different sets of spots. Specifically, if the reconstructed image shows crystal structures from different regions of the same sheet, it is a polycrystalline material. Otherwise, it is a turbostratic material.

[0308] (2) HR-TEM can be performed from the top view. Moiré patterns can be observed for turbostratic materials, but not for polycrystals. There are many different types of Moiré patterns. The Moiré pattern produced by only one rotational stacking fault is the simplest type with a period λ and a rotation angle θ. More complex Moiré patterns can be observed for more than two rotational orientations.

[0309] (3) Fourier transform can be performed at different positions of the sample in the same image, and the obtained diffraction patterns can be compared in reciprocal space. Specifically, if all diffraction patterns are not the same (orientation and number of points), it belongs to a polycrystal. Otherwise,

[0310] It is turbostratic material.

[0311] Schemes (2) and (3) are used to demonstrate the turbostratic characteristics of flash samples.

[0312] To identify the turbostratic structure [Ci 2010; Warner 2009], HR-TEM atomic top view images were performed. In-plane Moiré patterns were observed from the few-layer region. The sharp fringes and FFT patterns indicate good crystallinity of the flash product. The FFT patterns were compared at different locations on the same slice. The possibility of polycrystallinity in this region was excluded due to the constant orientation and number of diffraction points. Therefore, each group of diffraction points is generated by the turbostratic structure.

[0313] Bright field (BF) and high angle annular dark field scanning transmission electron microscopy (HAADF-STEM) images together with elemental mapping indicate the presence of B, N, and a small amount of C in the f-BN flakes. Fig.16J ), which is consistent with the XPS results.

[0314] Plate-like f-BN with lateral dimensions of 20 to 50 nm were also observed. HR-TEM images show the crystallinity of the f-BN nanosheets, most of which are only a few layers thick. The corresponding FFT images show at least three sets of sextupled diffraction patterns. The estimated mass yield of f-BN is ~34%. The conductive carbon additive can be removed from f-BN by heat treatment under air. However, oxidation will occur simultaneously on the surface. See Table VI. There are a small number of BC and BO bonds in f-BN, which is reasonable because previous studies have shown that oxidation of BC bonds begins at ~600°C [Hu 2019; Li 2014].

[0315] Table VI

[0316] Element content after heat treatment

[0317] B N O C Commercial h-BN 46.0% 47.1% 5.2% 1.7% f-BN 34.7% 12.5% 46.6% 6.1% <![CDATA[BH3NH3]]> 44.9% 46.4% 6.4% 2.3%

[0318] Mechanical peeling test of f-BN

[0319] The turbostratic character of f-BN facilitates its exfoliation by various mechanical methods, such as tape peeling, unidirectional mechanical shearing, and bath sonication.

[0320] Table VII

[0321] Results of mechanical peel test

[0322] f-BN Industrial h-BN Tape peeling yes no Mechanical shearing yes no Bath sonication (without surfactant) yes no

[0323] The few-layer f-BN sheets obtained by tape stripping can be used with Fig.17A In contrast, due to the strong coupling between adjacent layers in commercial h-BN, there is no obvious debonding and Fig. 17B Only nanoplates a few hundred nanometers thick were observed in the 3D images. The average lateral sizes of f-BN and commercial h-BN obtained by tape exfoliation were 0.40 and 0.34 μm, respectively. Fig. 17C (Circles 1701-1702 for f-BN and h-BN, respectively.) The size distribution results show that most f-BN flakes have lateral dimensions no larger than 1.0 μm, which makes them difficult to use in electronic devices such as field effect transistors. [Gupta 2020].

[0324] However, the advantages of f-BN, such as nanoscale features and good dispersibility, suggest the potential application of f-BN as a nanofiller to enhance mechanical properties and improve electrochemical anti-corrosion performance, as discussed below.

[0325] The same exfoliation phenomenon can be observed by applying uniaxial shear force. Fig.17D , showing exfoliated f-BN sheets with identical edge features (depicted by the white dashed lines 1711 outlining each sheet). The direction of the unidirectional shear force is given by Fig.17D As shown by arrow 1712 in FIG. 1 . Atomic force microscopy (AFM) images show the bilayer to few-layer characteristics of the exfoliated f-BN sheets. These results indicate the effective exfoliation of f-BN. In contrast, few-layer BN sheets cannot be directly prepared from commercial h-BN by unidirectional shearing under the same conditions ( Fig.17E ). The average lateral sizes of f-BN and commercial h-BN obtained by mechanical shearing method are 0.47 and 0.40 μm, respectively. Fig.17F (Circles 1721-1722 for f-BN and h-BN, respectively).

[0326] Compared with commercial h-BN nanosheets with >10 layers, few-layer f-BN flakes with a corrugated structure of a few hundred nanometers were obtained by bath sonication in surfactant-free ethanol. Figures 17G-17H The layer number distribution of f-BN obtained by bath sonication showed that ~80% of the f-BN sheets had 3-5 layers. Fig.17I In some areas, small black particles can be found, presumably from carbon conductive additives. The HR-TEM images and corresponding FFT patterns demonstrate the high quality of the turbostratic f-BN sheets and the well-aligned structure of the commercial h-BN nanosheets.

[0327] Electrochemical Corrosion Test of f-BN Composites

[0328] The turbostratic character improves the dispersibility and stability of f-BN in aqueous solution. After dispersion in aqueous Pluronic (F-127) (1 wt % in deionized water), the concentration of f-BN can be up to ~18 wt % higher than commercial h-BN. The percentages of commercial h-BN and f-BN still in solution after 21 days are ~6% and 77%, respectively, indicating that the f-BN dispersion has a higher temporal stability. The good dispersibility of f-BN allows the preparation of stable nanocomposites with f-BN as a compatibilizing additive.

[0329] A prerequisite is the dispersion and distribution of nanofillers within the polymer matrix, as the reinforcement of the composite relies on the filler surface area and the interactions between the polymers. [Luong 2020; Albdullah 2018]. PVA has been studied as a model system for surface coatings to test additives to reduce chemical and electrochemical metal corrosion. [Sarkar 2016; Owuor 2017]. Barrier films provide a tortuous diffusion path for corrosive electrolytes, delaying the metal corrosion process. Likewise, they prevent the migration of metal ions, thereby establishing a local Nernst potential at the polymer-metal interface. The addition of appropriate nanofillers can occupy the free volume within the polymer matrix and improve the barrier properties of the film. [Sarkar 2016].

[0330] Since f-BN shows good dispersibility in aqueous solution, Figures 18A-18D f-BN was further shown in as a filler in PVA composites, which were used as electrochemical anti-corrosion coatings.

[0331] Before electrochemical testing, the coating thickness was characterized by cross-sectional SEM images. The average thickness of the coating was ~9 μm. Electrochemical linear polarization resistance (LPR) tests of bare Cu, PVA-coated Cu (Cu-PVA), commercial h-BN and PVA composite-coated Cu (Cu-PVA-h-BN), and f-BN and PVA composite-coated Cu (Cu-PVA-f-BN) in 3.5 wt% salt solution are shown in Figures 19A-19D Cu-PVA-f-BN exhibits the largest polarization resistance (R p )~22.8kΩcm 2 , which is ~47% higher than Cu-PVA.

[0332] Open circuit potential (E corr ) represents the thermodynamic tendency of the electrode to lose electrons to the solution. [Warner 2009; Li 2014]. According to the Nernst equation, when the measured potential is lower than E corr The metal surface remains relatively stable. Fig.18A (The curves of bare Cu, Cu-PVA, Cu-PVA-h-BN and Cu-PVA-f-BN are 1801-1804 respectively) and Fig.18B The potentiodynamic polarization measurements in (the curves for bare Cu, Cu-PVA, Cu-PVA-h-BN, and Cu-PVA-f-BN are 1811-1814, respectively) show that Cu-PVA-f-BN has a more positive E corr (-188 mV vs Hg / Hg2SO4), so the surface metal has less tendency to participate in the electrochemical oxidation process. Compared with pure PVA and PVA-h-BN composite coatings, PVA-f-BN composites have higher corrosion protection efficiency (>92%) and better corrosion resistance, as shown in Table VIII.

[0333] Table VIII

[0334] Electrochemical parameters determined by potentiodynamic polarization for bare Cu, Cu-PVA, Cu-PVA-h-BN and Cu-PVA-f-BN in 3.5 wt% NaCl(Aq)

[0335]

[0336] The same enhanced corrosion resistance trend was also observed in 0.5M H2SO4, as Fig.18C (The curves of bare Cu, Cu-PVA, Cu-PVA-h-BN and Cu-PVA-f-BN are 1821-1824 respectively) and Fig.18D(The curves of bare Cu, Cu-PVA, Cu-PVA-h-BN and Cu-PVA-f-BN are 1831-1834 respectively). Cu-PVA-f-BN exhibits the largest polarization resistance (R p )~10.0kΩcm 2 , which is >20 times higher than Cu-PVA. As shown in Table IX, the corrosion protection efficiency of Cu-PVA-f-BN is >97%, while the corrosion protection efficiency of Cu-PVA-h-BN is 68%. This further demonstrates the excellent dispersibility and compatibility of f-BN in the polymer matrix.

[0337] Table IX

[0338] Electrochemical parameters of bare Cu, Cu-PVA, Cu-PVA-h-BN and Cu-PVA-f-BN determined by potentiodynamic polarization in 0.5 M H2SO4

[0339]

[0340] Optical and microscopic morphology after electrochemical testing showed that Cu under the PVA-f-BN composite coating was minimally affected, and surface elemental analysis also showed no obvious formation of Cu-PVA-f-BN oxides. These results are consistent with the highest corrosion protection efficiency from electrochemical testing and demonstrate a potential application of f-BN as a filler for nanocomposites.

[0341] Mechanical properties such as hardness and Young's modulus of epoxy resin with 1 wt% f-BN additive showed an increase of 54% and 70%, respectively, compared to neat epoxy resin. These improvements could not be achieved by replacing f-BN with an equal amount of commercial h-BN.

[0342] Synthesis of f-BCN with different chemical compositions

[0343] The atomic ratio of carbon can be adjusted by directly changing the weight percentage of carbon black in the reactants. If a mixture of BH3NH3 and 30 wt% carbon black is used as the reactant, the flash product is called f-BCN-30. The same naming convention is used here for other f-BCN samples prepared. As the weight percentage of carbon increases, the atomic percentage of carbon in the flash product can be controlled from ∼0% to ∼100% as determined by XPS results. Fig. 20A (f-BN-W, f-BN, f-BCN-50 and f-BCN-100 are insets 2001-2004, respectively). Elemental analysis shows that B and N decrease monotonically from f-BN to f-BCN-100. Fig. 20BThe high-resolution XPS of C 1s spectra showed the presence of CB and CN bonds in the f-BCN samples. As the mass ratio of carbon increased, the CB to CN ratio also increased. The high-resolution XPS of B 1s and N1s spectra also confirmed the presence of BC and NC bonds.

[0344] The presence of BC and NC bonds confirms the formation of an in-plane hybrid structure rather than an out-of-plane stacked heterostructure, which is generally more thermodynamically stable. This can be attributed to the ultrafast heating and cooling rates of the FJH reaction (~10 4 Ks -1 ).

[0345] After the reaction between carbon black and BH3BH3, there are several possibilities for the flash product, namely:

[0346] (1) A mixture of BN and carbon black.

[0347] (2) Mixture of NC, BC, BN and graphene or carbon black.

[0348] (3) Boron-carbon-nitrogen ternary compounds and carbon black.

[0349] High-resolution XPS results reflect the presence of BC, BN, and CN bonds, which excludes the possibility that the product is a mixture of BN and carbon black alone.

[0350] For NC and BC, there are two possibilities. First, BC and NC can be boron carbide and carbon nitride. Boron carbide has a covalent B4C part at ~187.4eV in the B1s spectrum, and it has a characteristic XRD peak (powder diffraction file 35-0798, B4C). However, the deconvolution results of the B 1s spectrum show that there is no peak at ~187.4eV and no characteristic XRD peak, which excludes the possibility of boron carbide. Similarly, there is no characteristic XRD peak of carbon nitride (powder diffraction file 50-1250, C3N4), which excludes the possibility of carbon nitride. Another possibility for BC and NC is co-doped graphene, which can be considered as a carbon-rich boron-carbon-nitrogen component.

[0351] The TEM images show the presence of conductive carbon materials with some graphite structures in the flash products. Taking f-BCN-30 as an example, the average size of the conductive carbon materials is ~25 nm, which is different from f-BCN-30. This observation indicates that there is unconverted carbon material in the flash products. Therefore, the flash products are a mixture of boron-carbon-nitrogen ternary compounds and carbon black. The presence of conductive carbon materials in the products can overestimate the carbon ratio determined by XPS analysis.

[0352] Due to the difference in thermal stability of conductive carbon materials and substituted carbon species chemically bonded to boron and nitrogen, thermogravimetric analysis (TGA) can be used to oxidize conductive carbon materials. The first derivative of the thermogravimetric curve shows two peaks starting from ~540°C and ~750°C, and the first peak is mainly attributed to the oxidation of conductive carbon materials. Therefore, under air conditions, by controlling the temperature at ~675°C, conductive carbon materials can be removed from the flash product (i.e., the carbon content of the carbon-rich boron-carbon-nitrogen ternary compound can be underestimated). The XPS results of various f-BCN samples before and after heat treatment reflect the presence of substituted carbon species. After heat treatment at ~675°C for 30 minutes under air conditions, the ratio of carbon content in f-BCN-70 can reach 35.7at%.

[0353] The carbon ratio of the in-plane hybrid structure affects the electronic structure and changes the VBM. As the carbon atomic ratio increases, the VBM of f-BCN changes from -3.10 eV to -1.85 eV. Fig. 20C The Raman spectra of different f-BCN samples show a G peak (~1580 cm -1 , single resonance), D peak (~1350cm -1 , valley double resonance), 2D peak (~2695cm -1 , second-order band boundary phonons), D+G peak (~2930cm -1 , combination of scattering peaks), 2D'(~3250cm -1 ) and G*(~2450cm -1 ) morphology. [Huang 2020; Hong2013; Yoon 2012]. As the carbon ratio in the reactants increases, the intensity of the D+G peak decreases and the intensity of the 2D peak increases. The intensity ratio of the D peak to the G peak of f-BCN-70 is ~1.10, which is similar to boron and nitrogen co-doped graphene and belongs to carbon-rich BCN. f-BCN-100 (FG) shows a high 2D to G ratio (~8) and a low D peak, which is similar to Luong 2020. The introduction of carbon into f-BCN samples also imparts magnetic properties [Sarkar 2016], which is different from commercial h-BN.

[0354] h-BN exhibits a diamagnetic response due to the total magnetic moment of ~0 due to the boron and nitrogen bonding. However, f-BCN-50 has BC / O and NC / O bonds, which may contribute to the total magnetic moment. f-BCN-50 shows a ferrimagnetic response with a small coercivity of ~22 Oe. The saturation magnetic moment of f-BCN-50 is 0.115 emu g -1. Inductively coupled plasma mass spectrometry (ICP-MS) confirmed the negligible contribution of magnetic metals such as Fe, Co, and Ni, as well as other d-block metals. [Fan 2019; Zhao 2014]. (HNO3 (67–70 wt%, TraceMetalTM grade, Fisher Chemical), HCl (37 wt%, 99.99% trace metal base, Millipore-Sigma), and water (Millipore-Sigma, ACS reagent for excess analysis) were used for sample digestion. All samples were digested using the dilute aqua regia method. The samples were soaked in HNO3 / HCl (1 M each) solution at 85°C for 6 h. The acidic solution was filtered to remove any undissolved particles. The solution was then diluted to the appropriate concentration range within the calibration curve using 2 wt% HNO3. ICP-MS was performed using a Perkin Elmer Nexion 300-ICP-MS system).

[0355] Fig.21 The boron-carbon-nitrogen ternary phase diagram in shows the chemical composition (boron, carbon and nitrogen) of different f-BCN products before heat treatment, demonstrating the broad accessibility of various BCN materials by the FJH method. Fig.21 , spheres 2101 and dots 2102 representatively refer to classical compounds and experimental results of embodiments as described herein. The atomic ratios were determined by XPS results.

[0356] All of these f-BCN samples have a turbostratic structure with large interlayer spacing, as the (002) diffraction peak shifts to lower angles with a broad (10) peak by XRD. The interlayer spacing of f-BCN is 3-6% larger than that in commercial h-BN, and f-BCN-50 has the largest interlayer spacing, which is ~6.1% larger than that in commercial h-BN. Fig.20D ; See also Table X.

[0357] Table X

[0358] Crystal structure of f-BCN sample

[0359]

[0360] 1 These values ​​show the percent change in interlayer spacing compared to commercial h-BN, where the percent change was calculated using Eq (7).

[0361] Percent change = (interlayer spacing f-BCN - Layer spacing h-BN ) / layer spacing h-BN ×100%(14)

[0362] The f-BCN samples have a large surface area (110-310 m 2 g -1 ), and they have abundant micropores and mesopores. Fig.20D The Moiré pattern can be seen from the HR-TEM image of the f-BCN sample ( Fig.20E ), which indicates the presence of a turbostratic stacking structure. The corresponding FFT pattern reflects multiple groups of diffraction points from the

[002] direction. Fig.20F Atomic-scale HR-TEM images show complex Moiré patterns and good in-plane crystallinity. Figure 20G The STEM images confirmed the unaligned edges, and the elemental mapping results indicated the presence of B, C, and N in the f-BCN-30 sample. Fig. 20H .

[0363] To confirm the presence of substituted carbon species in the structure and exclude hydrocarbon contamination caused by false positive carbon signals, electron energy loss spectroscopy (EELS) was performed, and the C K-edge spectrum showed the presence of 1s-π* peaks and 1s-σ* peaks, which indicated the presence of substituted carbon atoms in the conjugated structure and excluded the possibility that the carbon signal was entirely from amorphous hydrocarbon contamination. [Langenhorsta 2002; McGilvery 2012].

[0364] Heteroatom doped (substituted) re-flash graphene

[0365] In an embodiment, the present invention also involves utilizing already synthesized flash graphene for a flash doping process. Thus, the carbon feedstock is initially flashed to convert it into turbostratic flash graphene. The flash graphene is then mixed with a heteroatom doping compound before undergoing a second flash. This new method achieves a higher doping rate than that achieved by the previously referenced single rapid doping method. A schematic diagram of the method is shown in Figures 22A-22B .

[0366] Synthesis of heteroatom-substituted re-flash graphene via FJH

[0367] The FJH system (and parameters) that can be used to synthesize heteroatom-substituted re-flashed graphene can be based on the system described and illustrated in the Tour '642 application and the Tour '111 PCT application, with modifications as described below. [See also Luong 2020; Chen 2022; Deng 2022]. The parameters / statements for heteroatom-substituted re-flashed graphene can include the following:

[0368] (1) After having been flash evaporated once, the flash evaporated graphene can be converted into doped flash evaporated graphene.

[0369] (2) The method can be implemented to varying degrees using a variety of different carbon raw materials and a variety of different doping compounds.

[0370] (3) When the weight ratio of doping compound to flash graphene is 1:4, the doping rate can usually be maximized.

[0371] (4) Amorphous carbon feedstocks with lower surface areas can usually have higher doping rates.

[0372] (5) In some embodiments, organic powders with low melting points can be the most effective doping compounds.

[0373] (6) In some embodiments, performing the doping flash reaction under an argon atmosphere may be desirable for higher doping rates.

[0374] (7) In some embodiments, amorphous carbon feedstock with smaller particle size may be less effective for initial graphene conversion, but may be more effective for subsequent doping.

[0375] (8) In some embodiments, doping flash can produce the highest doping rate when flashed once at about 3 kJ / g and then flashed again at about 16 kJ / g.

[0376] (9) The re-flash method can be performed using pulse width modulated DC electrical pulses from the capacitor bank discharge, and can also be performed using modulated or non-modulated AC and DC current sources.

[0377] The synthesized heteroatom-substituted re-flashed graphene uses flashed graphene instead of amorphous carbon as the initial reactant, allowing a higher doping rate to be achieved. The flashed graphene used for re-flashing can be flashed graphene synthesized by FJH, including but not limited to the flashed graphene described above for 1D carbon nanomaterials, the flashed graphene described in the Tour'642 patent, and the flashed graphene with holes and wrinkles described in the Tour'987 PCT application.

[0378] For example, in embodiments, a desired carbon raw material is selected for graphene conversion. To achieve high doping rates, two raw materials for graphene that have been found to be metallurgical coke (MC) and asphaltene activated carbon (BAC) as described herein, but this can vary and include plastic derived flash graphene, holey and wrinkled flash graphene (HWFG), or graphene obtained from any source and any method. Fig.23 Schematic diagrams of the reaction vessels for both are shown in FIG. Fig.23 In the embodiment of the present invention, the graphite electrode 2302, the copper electrode 2301 and the feedstock 2304 (in the quartz tube 2303) are all conductive enough to allow the current required for Joule heating to pass. Graphite and copper are more conductive than the feedstock sufficiently so that most of the heat is consumed in the feedstock. Copper helps to provide more uniform electrical contact and more effectively maintains smaller feedstock particles.

[0379] In an exemplary method using metallurgical coke, several kilograms of metallurgical coke blocks are obtained from Suncoke. The metallurgical coke is then ground and sieved until the particle size diameter is 0.84-1.68 mm. The coke is then placed in a fused quartz tube with an inner diameter of 16 mm and a length of about 10 cm, and the tube is closed at either end with two graphite electrodes. The sample is then compressed until it reaches 1.3Ω. The metallurgical coke is reacted in this container by flash Joule heating with a batch size of 5.7 g at 7.5 kJ / g, using a pulse width modulation signal divided into 3 duty cycles, the duty cycle being 10% for 1 s, 20% for 0.5 s, and 50% for 5 s. The resulting flash graphene is determined by Raman spectroscopy analysis to be ~99% converted into turbostratic flash graphene.

[0380] In an exemplary process using asphaltene activated carbon, an asphaltene activated carbon with a particle size of about 1-2 mm diameter was obtained. This was then filled into a flash vessel in 4.2 gram batches, compressed to 1.0 Ω, and flashed at 7.5 kJ / g in the same duty cycle as used for metallurgical coke. Graphene conversion was also measured to be ~99%.

[0381] Once the flash graphene was made, it initially remained in particles that were too large for efficient mixing. Therefore, it was placed in a planetary ball mill among steel balls for 60 minutes to reduce its size to particles less than 0.2 mm in diameter.

[0382] Thereafter, the heteroatom compound or a combination of different compounds (for co-doping) is then mixed with flash graphene in a 1:4 weight ratio in batches of 200 mg by a mortar and pestle. Boric acid is used for boron doping, melamine resin is used for nitrogen doping, polyphenylene sulfide is used for sulfur doping, and perfluorooctanoic acid is used for fluorine doping. These compounds are selected for testing as described herein based on their low decomposition temperature compared to other tested doping compounds and the high doping rates they achieve. However, there is no particular restriction on the dopant materials that can be used, and the dopant used in the present invention is not limited to the dopant selected for testing.

[0383] 200 mg of this mixture was then loaded into a quartz tube about 4 cm long and 8 mm inner diameter. A thin copper wire was then rolled into a small electrode 8 mm in diameter and ~4 mm thick at either end, which was in electrical contact with the raw material. A small graphite column 8 mm in diameter and ~8 mm long was then placed at either end of the quartz tube and in electrical contact with the copper electrode. The resulting container was placed between two electrodes connected to a flash Joule heating system and compressed until the measurement was below 5 Ω. The container was then placed under an argon atmosphere.

[0384] Thereafter, flash Joule heating was performed in two steps to maximize yield. The first pretreatment flash was performed at ~3.1 kJ / g, and the second, primary flash was performed at ~15.6 kJ / g. The flash reaction was performed using a pulse width modulated discharge with a 3-step duty cycle mode of 10% for 1 s, 20% for 0.5 s, and 50% for 5 s. Figures 24A-24B The difference between this flash evaporation and the flash evaporation performed in step 1 is explained in FIG.

[0385] Characterization of heteroatom substituted re-flash graphene

[0386] Standard characterization tools were used to verify the conversion of the resulting products into graphene and the doping of graphene with heteroatoms. Figures 25A-25C Raman and X-ray photoelectron spectroscopy (XPS) analysis of N-doped BAC-derived re-flash graphene is shown. Fig.25A As shown, the presence of D, G, and 2D Raman peaks, as well as the height of the 2D peak relative to the height of the G peak, indicate that the sample was converted to high-quality graphene (a high 2D peak is a positive indicator of graphene). Fig.25B The presence of TS1 and TS2 Raman peaks is shown, which further indicates that the stacking of graphene layers is turbostratic (disordered) in nature. Fig.25C The doping of nitrogen in the graphene lattice is illustrated in Figure 2 (curves 2501-2504 for N1a, graphite, pyrrole and pyridine respectively), further illustrating the bonding nature of nitrogen bonding. From the XPS spectrum analysis, the N doping percentage in this sample was calculated to be ~5%, which means that 5% of the atoms present in the sample are nitrogen.

[0387] The morphology and elemental composition of the products were further verified by using scanning electron microscopy (SEM) and energy dispersive X-ray spectroscopy (EDX). Figures 26A-26C As shown, it shows N-doped BAC-derived re-flashed graphene. EDX analysis shows that N atoms are evenly distributed across the surface of the graphene (carbon) sample. The fading around the edge of the sample is due to the sample being outside the focus outside the center. Using these methods, this confirms that the product confirmed as graphene by Raman spectroscopy analysis is mainly composed of C, but also shows N atoms near the surface. In addition to XPS analysis, this analysis is also used to confirm the presence of nitrogen in the product.

[0388] Figures 27A-27B Analysis of N-doped MC derived re-flash graphene is shown. The graphene nature of the product is again confirmed by Raman spectroscopy analysis (high 2D peaks are again a positive indicator of graphene), and Fig.27B XPS spectral analysis of (curves 2701-2703 for N1a, graphite and pyrrole, respectively) confirms that this sample has a particularly high doping ratio of almost 28%.

[0389] In the embodiments tested, Fig.28 The results for the best doping rates obtained are summarized in , which include results from co-doping experiments during the doping of several different heteroatoms into the graphene lattice at once. ( Fig.28 The right portion (labeled "BACFG") shows co-doping of multiple different types of heteroatoms.) In the embodiments tested, doping reactions were generally more successful using flash graphene derived from metallurgical coke than flash graphene derived from asphaltene activated carbon.

[0390] application

[0391] There are various applications for the method and the resulting products. The present invention solves the problem of effectively achieving high doping rates (above 10%) in heteroatom-doped graphene. In addition, the method is easily scaled up and can be used to produce large quantities of doped graphene. Furthermore, the low price of the raw materials required to produce the heteroatom-doped graphene allows the method to effectively compete with other methods of producing doped graphene.

[0392] Furthermore, possible applications of the resulting heteroatom-substituted re-flashed graphene include use as an additive to concrete and epoxy resin to increase mechanical strength and for battery electrode materials to increase performance.

[0393] Furthermore, the ability to dope graphene with a variety of heteroatom compounds also provides the opportunity to upcycle organic waste sources into heteroatom-substituted re-flash graphene via FJH (as described above).

[0394] Although embodiments of the present invention have been shown and described, those skilled in the art may modify them without departing from the spirit and teachings of the present invention. The embodiments described herein and the examples provided are exemplary only and not restrictive. Many variations and modifications of the present invention disclosed herein are possible and are within the scope of the present invention. The scope of protection is not limited by the above description, but only by the appended claims, which include all equivalents of the claimed subject matter.

[0395] The disclosures of all patents, patent applications, and publications cited herein are incorporated by reference in their entirety, to the extent they provide exemplary, procedural or other details supplementary to those set forth herein.

[0396] Quantity and other numerical data can be expressed in range format here.It should be understood that the use of this range format is only for convenience and simplicity, and should be flexibly interpreted as not only including the numerical values ​​clearly listed as the limits of the range, but also including all single numerical values ​​or sub-ranges contained in the range, as if each numerical value and sub-range are clearly listed.For example, the numerical range of about 1 to about 4.5 should be interpreted as not only including the clearly listed limits of 1 to about 4.5, but also including individual numbers such as 2, 3, 4, and sub-ranges such as 1 to 3, 2 to 4, etc. The same principle applies to the range of only narrating a numerical value, such as "less than about 4.5", which should be interpreted as including all the above values ​​and ranges.In addition, no matter how the width of the range or the characteristics described, this interpretation should be applied.

[0397] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which the disclosed subject matter belongs. Although any methods, devices, and materials similar or equivalent to those described herein can be used in the practice or testing of the disclosed subject matter, representative methods, devices, and materials are now described.

[0398] Following long-standing patent law convention, when used in this application, including the claims, the terms "a" and "an" mean "one or more."

[0399] Unless otherwise indicated, all numbers expressing quantities of ingredients, reaction conditions, and so forth used in the specification and claims are to be understood as being modified in all instances by the term “about.” Accordingly, unless indicated to the contrary, the numerical parameters set forth in the specification and attached claims are approximations that may vary depending upon the desired properties sought to be obtained by the presently disclosed subject matter.

[0400] As used herein, the terms "about" and "substantially," when referring to a value or amount of mass, weight, time, volume, concentration, or percentage, are intended to encompass variations of ±20% in some embodiments, ±10% in some embodiments, ±5% in some embodiments, ±1% in some embodiments, ±0.5% in some embodiments, and ±0.1% in some embodiments from the specified amount, as such variations are suitable for performing the disclosed methods.

[0401] As used herein, the terms "substantially perpendicular" and "substantially parallel" mean that in some embodiments, variations within ±10° of the perpendicular and parallel directions, respectively, in some embodiments, variations within ±5° of the perpendicular and parallel directions, respectively, in some embodiments, variations within ±1° of the perpendicular and parallel directions, respectively, and in some embodiments, variations within ±0.5° of the perpendicular and parallel directions, respectively.

[0402] As used herein, the term "and / or" when used in the context of a list of entities refers to the entities being present individually or in combination. Thus, for example, the phrase "A, B, C, and / or D" includes A, B, C, and D individually, but also includes any and all combinations and subcombinations of A, B, C, and D.

[0403] References

[0404] U.S. patent application publication No. 2021 / 0206642, filed on March 2, 2021 and published on July 8, 2021, to Tour et al., entitled “Flash Joule Heating Synthesis Method And Compositions Thereof,” (“Tour '642 Application”).

[0405] PCT International Patent Publication No. WO 2022 / 067111, filed on September 24, 2021, granted to JM Tour, et al., entitled “Ultrafast Flash Joule Heating Methods And System For Performing Same” (“Tour’111 PCT Application”).

[0406] PCT International Patent Application No. PCT / US / 64987, filed on March 27, 2023, granted to JM Tour et al., entitled “Ultrafast Synthesis Of Holey And Wrinkled Graphene (“Tour '987 PCT Application”).

[0407] Advincula, PA, et al., Carbon, 2021, 178, 649 ("Advincula 2021").

[0408] Agnoli, S, et al., Journal of Materials Chemistry A, 2016, 4, 5002-5025 (“Agnoli 2016”).

[0409] Ahamed,A.,et al.,J.Hazard.Mater.,2020,390,121449("Ahamed 2020").

[0410] Ahn, J., et al., J. Appl. Phys., 2000, 87, 4022 ("Ahn 2000").

[0411] Ajayan,P.M.,et al.,in Carbon Nanotub.Synth.Struct.Prop.Appl.(Eds.:M.S.Dresselhaus,G.Dresselhaus,P.Avouris),Springer,Berlin,Heidelberg,2001,pp.391-425(“Ajayan 2001”).

[0412] Alabdullah,F.T.,Exfoliated Hexagonal Boron Nitride Based Anti-corrosion Polymer Nano-composite Coatings for Carbon Steel in a SalineEnvironment,Colorado School of Mines(2018)(“Alabdullah 2018”).

[0413] Algozeeb,W.A.,et al.,ACS Nano,2020,14,15595(“Algozeeb 2020”).

[0414] Alkoy,S.,et al.,J.Eur.Ceram.Soc.,1997,17,1415(“Alkoy 1997”).

[0415] Arenal,R.,et al.,Nano Lett.,2006,6(8),1812-1816(“Arenal 2006”).

[0416] Ashraf,M.A,et al.,Nanoscale Res.Lett.,2018,13,214(“Ashraf 2018”).

[0417] Ba,K.,et al.,Sci.Rep.,2017,7,45584(“Ba 2017”).

[0418] Bae,D.S.,et al.,Nano Converg.,2022,9(1),20(“Bae 2022”).

[0419] Bazargan,A,et al.,Chem.Eng.J.2012,195-196,377(“Bazargan 2012”).

[0420] Beckham,JL,et al.,Adv.Mater.,2022,34,2106506(“Beckham 2022”).

[0421] Brar,VW,et al.,Phys.Rev.B,2002,66,155418(“Brar 2002”).

[0422] Cai,N.,et al.,Energy Convers.Manag.,2021,229,113794(“Cai 2021”).

[0423] Cai,QR,et al.,Nanoscale,2017,9,3059(“Cai 2017”).

[0424] Carozo,V.,et al.,Nano Lett.,2011,11,4527(“Carozo 2011”).

[0425] Carroll,KM,et al.,Langmuir,2018,34,73(“Carroll 2018”).

[0426] Cao,CC,et al.,2D Mater.,2022,9,015014(“Cao 2022”).

[0427] Chen,W.,et al.,ACS Nano,2022,16,6646(“Chen 2022”).

[0428] Chen,W.,et al.,ACS Nano,2021,15,11158(“Chen I 2021”).

[0429] Chen,W.,et al.,ACS Nano,2021,15,1282(“Chen II 2021”).

[0430] Chen,X.,et al.,Sci.Rep.,2017,7(1),1-9(“Chen 2017”).

[0431] Chen,X.,et al.,Appl.Phys.Lett.,2015,107(25),253105(“Chen 2015”).

[0432] Chen,Y.,et al.,Chem.Phys.Lett.,1999,299(3-4),260-264(“Chen 1999”).

[0433] Chiang,W.-H,et al.,Nat.Mater.,2009,8,882(“Chiang 2009”).

[0434] Chilkoor,G.,et al.,ACS Nano,2020,14,14809(“Chilkoor 2020”).

[0435] Chopra,NG,et al.,Science,1995,269(5226),966-967(“Chopra 1995”).

[0436] Ci,LJ,et al.,Nat.Mater.,2010,9,430(“Ci 2010”).

[0437] Constantinescu,G.,et al.,Phys.Rev.Lett.,2013,111,036104(“Constantinescu 2013”).

[0438] Demirci,UB,Energies,2020,13(12),3071(“Demirci 2020”).

[0439] Deng,B.,et al.,Nat.Commun.,2022,13(1),262(“Deng 2022”).

[0440] Deng,B.,et al.,Nat.Commun.,2021,12,5794(“Deng 2021”).

[0441] Ding,W.,et al.,Nat.Commun.2021,12,5886(“Ding 2021”).

[0442] Ding,W.,et al.,ACS Nano,2019,13,1694(“Ding 2019”).

[0443] Edgar,JH,Properties of group III nitrides(1994)(“Edgar 1994”).

[0444] Fathalizadeh,A.,et al.,Nano Lett.,2014,14(8),4881-4886(“Fathalizadeh2014”).

[0445] Fan,MM,et al.,Adv.Mater.,2019,31,1805778(“Fan 2019”).

[0446] Feng,L.,et al.,Materials,2014,7,3919(“Feng 2014”).

[0447] Ferrari,AC,et al.,Nat.Nanotechnol.,2013,8,235(“Ferrari 2013”).

[0448] Fouquet,M,et al.,Phys.Rev.B,2012,85,235411(“Fouquet 2012”).

[0449] Frueh,S.,et al.,Inorg.Chem.,2011,50(3),783-792(“Frueh 2011”).

[0450] Gladkaya,IS,et al.,J.Alloys Compd.,1986,117,241(“Gladkaya 1986”).

[0451] Gong,J,et al.,Ind.Eng.Chem.Res.,2013,52,15578(“Gong 2013”).

[0452] Gorbachev,RV,et al.,Small,2011,7,465(“Gorbachev 2011”).

[0453] Govind Rajan,A.,et al.,J.Phys.Chem.Lett.,2018,9,1584(“Govind Rajan2018”).

[0454] Guo,Y.,et al.,Sci.Rep.,2022,12,2522(“Guo 2022”).

[0455] Gupta,S.,et al.,ACS Appl.Nano Mater.,2020,3,7930(“Gupta 2020”).

[0456] Han,X.,et al.,ACS Nano,2018,12,11,11219(“Han 2018”).

[0457] Hong,J.,et al.,Sci.Rep.,2013,3,2700(“Hoon 2013”).

[0458] Hu,S.-Q.,et al.,J.Chem.,2019,2019,8793282(“Hu 2019”).

[0459] Huang,L.,et al.,ACS Nano,2020,14,12045(“Huang 2020”).

[0460] Huang,Y.,et al.,Nanotechnology,2011,22(14),145602(“Huang2011”).

[0461] Hunter,RD,et al.,J.Mater.Chem.A,2022,10,4489(“Hunter2022”).

[0462] Jagodzinska,K,et al.,Chem.Eng.J.,2022,446,136808(“Jagodzinska 2022”).

[0463] Jia,M.,et al.,Macromol.Rapid Commun.,2022,43,2100835(“Jia 2022”).

[0464] Jia,Z.,et al.,Catalysts,2017,7,256(“Jia 2017”).

[0465] Jie,X.,et al.,Nat.Catal.,2020,3,902(“Jie 2020”).

[0466] Kakiagea,M.,et al.,Key Eng.Mater.,2013,534,55(“Kakiagea 2013”).

[0467] Khanna,V.,et al.,Journal of Industrial Ecology,2008,12(3),394-410(“Khanna 2008”).

[0468] Kim,H.-S.,et al.,Nanomaterials(Basel,)2021,12(1),11(“Kim H 2021”).

[0469] Kim,J.,et al.,Acta Mater.,2011,59(7),2807-2813(“Kim 2011”).

[0470] Kim,JH,et al.,Sci.Rep.,2019,9(1),15674(“Kim 2019”).

[0471] Kim,JH,et al.,Nano Converg.,2018,5(1),17(“Kim J 2018”).

[0472] Kim,KS,et al.,ACS Omega,2021,6(41),27418-27429(“Kim K 2021”).

[0473] Kim,KS,et al.,ACS Nano,2018,12(1),884-893(“Kim K 2018”).

[0474] Kim,M.,et al.,Chem.Eng.J.,2020,395,125148(“Kim 2020”).

[0475] Koepke,JC,et al.,Chem.Mater.,2016,28(12),4169-4179(“Koepke 2016”).

[0476] D.,et al.,ACS Appl.Nano Mater.,2022,5(2),2137-2146(“ 2022”).

[0477] Kosynkin,DV,et al.,Nature,2009,458,872(“Kosynkin 2009”).

[0478] Kou,L.,et al.,Nano-Micro Lett.,2017,9,51(“Kou 2017”).

[0479] Kour,R.,et al.,J.Electrochem.Soc.,2020,167,037555(“Kour2020”).

[0480] Koutsioukis,A.,et al.,Nanomaterials,2022,12,447(“Koutsioukis 2022”)

[0481] Kumar,S.,et al.,Chem.Eng.J.,2021,403,126352(“Kumar 2021”).

[0482] Lahiri,D.,et al.,Acta Biomater.,2010,6(9),3524-3533(“Lahiri 2010”).

[0483] Langenhorsta,F.,et al.,Phys.Chem.Chem.Phys.,2002,4,5183(“Langenhorsta2002”).

[0484] Lebedev,AV,et al.,ECS J.Solid.State.Sci.Technol.,2020,9,083004(“Lebedev 2020”).

[0485] Lee,CH,et al.,Molecules,2016,21(7),922(“Lee 2016”).

[0486] Lee,J.-K.,et al.,IUCrJ,2021,8(Pt 6),1018-1023(“Lee J 2021”)

[0487] Lee,S.-H.,et al.,Carbon,2021,173,901(“Lee S 2021”).

[0488] Li,L.,et al.,ACS Nano,2014,8,1457(“Li 2014”).

[0489] Li,T.,et al.,Nat.Energy,2018,3,148(“Li 2018”).

[0490] Li,Y.,et al.,E3S Web Conf.,2021,260,03027(“Li 2021”).

[0491] Li,Y.,et al.,Earth Environ.Sci.,2020,453(1),012091(“Li 2020”).

[0492] Lian,JB,et al.,J.Phys.Chem.C,2009,113,9135(“Lian 2009”).

[0493] Liu,F.,et al.,Front.Chem.,2021,9(“Liu 2021”).

[0494] Lourie,OR,et al.,Chem.Mater.,2000,12(7),1808-1810(“Lourie 2000”).

[0495] Call,DX,et al.,Nature,2020,577,647(“Call 2020”).

[0496] Martín-Lara,MA,et al.,J.Clean.,Prod.2022,365,132625(“Martín-Lara2022”).

[0497] McGilvery,CM,et al.,Micron,2012,43,450(“McGlvery 2012”).

[0498] McLean,B.,et al.,J.Appl.Phys.,2021,129,044302(“McLean 2021”).

[0499] Medupin,RO,et al.,Sci.Rep.,2019,9,20146(“Medupin 2019”).

[0500] Merlen,A.,et al.,Coatings,2017,7,153(“Merlen 2017”).

[0501] Mueller,J.E,et al.,J.Phys.Chem.C,2010,114,4939(“Mueller 2010”).

[0502] Owuor,P.S.,et al.,ACS Nano,2017,11,8944(“Owuor 2017”).

[0503] Pakdel,A.,et al.,Nanotechnology,2012,23(21),215601(“Pakdel 2012”).

[0504] Park,H.J.,et al.,Sci.Adv.,2020,6,eaay4958(“Park 2020”).

[0505] Plimpton,S.,J.Comput.Phys.,1995,117,1(“Plimpton 1995”).

[0506] Puyoo,G.,et al.,Carbon,2017,122,19(“Puyoo 2017”).

[0507] Rao,R.,et al.,ACS Nano,2018,12,11756(“Rao 2018”).

[0508] Rathinavel,S.,et al.,Mater.Sci.Eng.B,2021,268,115095(“Rathinavel2021”).

[0509] Ren,S.M.,et al.,ACS Appl.Mater.Interfaces,2017,9,27152(“Ren 2017”).

[0510] Restivo,J.,et al.,Processes,2020,8,1329(“Restivo 2020”).

[0511] Roy,S,et al.,Nanotechnol.Rev.,2018,7,475(“Roy 2018”).

[0512] Rubio,A.,et al.,Phys.Rev.B Condens.Matter,1994,49(7),5081-5084(“Rubio1994”).

[0513] Ruiz-Cornejo,J.C.,et al.,Rev.Chem.Eng.,2020,36,493(“Ruiz-Cornejo2020”).

[0514] Rydberg,H.,et al.,Phys.Rev.Lett.,2003,91,126402(“Rydberg 2003”).

[0515] Sarkar,N.,et al.,Ind.Eng.Chem.Res.,2016,55,2921(“Sarkar 2016”).

[0516] Sharma,S.S.,et al.,J.Chem.Technol.Biotechnol.,2020,95,11(“Sharma2020”).

[0517] Shi,C.,et al.,Small,2019,15,1902348(“Shi 2019”).

[0518] Singh,D.K.,et al.,Diam.Relat.Mater.,2010,19,1281(“Singh 2010”).

[0519] Shiratori,T.,et al.,Nanomaterials(Basel),2021,11(3),651(“Shiratori2021”).

[0520] Simpson,A.Stuckes,J.Phys.C:Solid State Phys.,1971,4,1710(“Simpson1971”).

[0521] Singh,N.K.,et al.,RSC Adv.,2018,8,17237(“Singh 2018”).

[0522] Smith,R.J.,et al.,Adv.Mater.,2011,23,3944(“Smith 2011”).

[0523] Song,L.,et al.,Nano Lett.,2010,10,3209(“Song 2010”).

[0524] Spahr,M.E.,et al.,Fillers for Polymer Applications.,375-400(2017)(“Spahr 2017”).

[0525] Stanford,M.G.,et al.,ACS Nano,2020,14(10),13691(“Stanford 2020”).

[0526] Stehle,Y.,et al.,Chem.Mater.,2015,27(23),8041-8047(“Stehle 2015”).

[0527] Tan,L.F.,et al.,Adv.Electron.Mater.,2015,1,1500223(“Tan 2015”).

[0528] Tay,R.Y.,et al.,Chem.Mater.,2015,27(20),7156-7163(“Tay 2015”).

[0529] Tay,R.Y.,et al.,J.Mater.Chem.C Mater.Opt.Electron.Devices,2014,2(9),1650-1657(“Tay 2014”).

[0530] Teah,H.,et al.,ACS Sustainable Chem.Eng.,2020,8(4),1730-1740(“Yeah2020”).

[0531] Temizel-Sekeryan,S.,et al.,Int J Life Cycle Assess,2021,26(4),656-672(“Temizel-Sekeryan 2021”).

[0532] Terao,T.,et al.,J.Phys.Chem.C,2010,114(10),4340-4344(“Tetao 2010”).

[0533] Thambiliyagodage,C.J.,et al.,Carbon,2018,134,452(“Thambiliyagodage2018”).

[0534] Thomas,J.,et al.,J.Am.Chem.Soc.,1963,84,4619(“Thomas 1963”).

[0535] Toyos-Rodríguez,C.,et al.,J.Nanomater.,2019,1-10(“Toyos-Rodríguez2019”).

[0536] Tripathi,P.K.,et al.,Nanomaterials,2017,7,284(“Tripathi 2017”).

[0537] Trompeta,A.-F.,et al.,Journal of Cleaner Production,2016,129,384-394(“Trompeta 2016”).

[0538] Vedhanarayanan,B.,et al.,NPG Asia Mater.,2018,10,107(“Vedhanarayanan2018”).

[0539] Viswanatha,R,et al.,John Wiley&Sons,Ltd,2007,pp.139-170(“Viswanatha2007”).

[0540] Wang,B,et al.,J.Am.Chem.Soc.,2007,129,9014(“Wang 2007”).

[0541] Wang,C.X.,et al.,J.Am.Chem.Soc.,2017,139,13997(“Wang 2017”).

[0542] Wang,J.,et al.,Catal.Today,2020,351,50(“Wang 2020”).

[0543] Wang,X.,et al.,Chemical Society Reviews,2014,43,7067-7098(“Wang2014”).

[0544] Wang,Y.,et al.,ACS Sustain.Chem.Eng.,2022,10,2204(“Wang 2022”).

[0545] Wang,Y.,et al.,J.Nanomater.,2008,2008,1-7(“Wang 2008”).

[0546] Wang,Z.,et al.,Nanomaterials,2019,9,1045(“Wang 2019”).

[0547] Warner,J.H.,et al.,Nano Lett.,2009,9,102(“Warner 2009”).

[0548] Williams,P.T.,Waste Biomass Valorization,2021,12,1(“Williams 2021”).

[0549] Wolfram Research,Inc.,Mathematica,Version 11.3,Champaign,IL(2018)(“Wolfram 2018”).

[0550] Wu,F.,et al.,Journal of Cleaner Production,2020,270,122465(“Wu2020”).

[0551] Wyss,K.M.,et al.,Adv.Mater.,2022,34(8),2106970(“Wyss I 2022”).

[0552] Wyss,K.M.,et al.,Commun.Eng.,2022,1,1(“Wyss II 2022”).

[0553] Wyss,K.M,et al.,ACS Nano,2022,16(5),7804(“Wyss III 2022”)

[0554] Wyss,K.M.,et al.,Carbon,2021,174,430(“Wyss I 2021”).

[0555] Wyss,K.M.,et al.,ACS Nano,2021,15,10542(“Wyss II 2021”).

[0556] Wu,C.,et al.,Process Saf.Environ.Prot.,2016,103,107(“Wu 2016”).

[0557] Wu,N.,et al.,Carbon,2021,176,88(“Wu 2021”).

[0558] Xia,K.,et al.,Procedia IUTAM,2017,21,94(“Xia 2017”).

[0559] Xie,H.,et al.,Small Methods,2018,2,1700371(“Xie 2018”).

[0560] Xu,D.,et al.,Angew.Chem.Int.Ed.,2018,57,755(“Xu D 2018”).

[0561] Xu,H.,et al.,Journal of Energy Chemistry,2018,27,146-160(“Xu H2018”).

[0562] Xu,Q.,et al.,Nanoscale,2019,11,1475(“Xu 2019”).

[0563] Yang,W.,et al.,J.Am.Chem.Soc.,2015,137,1436(“Yang 2015”).

[0564] Jacob, L., et al., ACS Omega, 2022, 7, 13403 (“Jacob 2022”).

[0565] Yan,Z.,et al.,ACS Nano,2014,8,5061(“Yan 2014”).

[0566] Yao,D.,et al.,ACS Sustain.Chem.Eng.,2022,10,1125(“Yao 2022”).

[0567] Yao,YG,et al.,Science,2018,359,1489(“Yau 2018”).

[0568] Yao,Y.,et al.,Nano Lett.,2016,16,7282(“Yao 2016”).

[0569] Ye,R.,et al.,ACS Nano 2019,13,10872-10878(“Ye 2019”).

[0570] Yoon,D.,et al.,Raman Spectroscopy for Characterization of Graphene,Springer-Verlag Berlin Heidelberg(2012)(“Yoon 2012”).

[0571] Yu,DP,et al.,Appl.Phys.Lett.,1998,72(16),1966-1968(“Yu 1998”).

[0572] Yuan,D.,et al.,Nano Lett.,2008,8,2576(“Yuan 2008”).

[0573] Zare,Y.,Compos.Part Appl.Sci.Manuf.,2016,84,158(“Zare 2016”).

[0574] Zeng,X.,et al.,ACS Nano,2017,11(5),5167-5178(“Zeng 2017”).

[0575] Zhao,C.,et al.,Adv.Funct.Mater.,2014,24,5985(“Zhao 2014”).

[0576] Zhao,M.-Q.,et al.,ACS Nano,2012,6,10759(“Zhao 2012”).

[0577] Zhi,C.,et al.,Adv.Funct.Mater.,2009,19(12),1857-1862(“Zhi 2009”).

[0578] Zhi,C.,et al.,J.Am.Chem.Soc.,2005,127(46),15996-15997(“Zhi 2005”).

[0579] Zhi,C.,et al.,Solid State Commun.,2005,135(1-2),67-70(“ZhiIII 2005”).

[0580] Zhong,B.,et al.,Mater.Des.,2017,120,266(“Zhong 2017”).

[0581] Zhu,M.,et al.,J.Inorg.Mater.,2019,34,817(“Zhu 2019”).

[0582] Zhuang,C.,et al.,RSC Adv.,2016,6(114),113415-113423(“Zhuang 2016”).

[0583] Zhuo,C.,et al.,J.Appl.Polym.Sci.,2014,131,DOI 10.1002 / app.39931(“Zhou2014”).

[0584] Zou,BJ,et al.,Prog.Org.Coat.,2019,133,139(“Zou 2019”).

Claims

1. A method comprising flash Joule heating a mixture of a material and a catalyst to form a 1-dimensional structure.

2. The method according to claim 1, wherein (a) the flash Joule heating is a process comprising applying a voltage across the mixture, which drives a current through the mixture to form a 1-dimensional structure; (b) applying a voltage in the form of one or more voltage pulses; and (c) The duration of each of the one or more voltage pulses is a duration period.

3. The method according to any one of claims 1-2, wherein the material is a carbon material that is substantially not graphene.

4. The method according to any one of claims 1 to 3, wherein the 1-dimensional structure is a graphite 1D and / or a hybrid material nanomaterial.

5. The method according to any one of claims 1-4, wherein the method further comprises forming the 1-dimensional structure form together with one or more other dimensional structures selected from 0-dimensional structure, 2-dimensional structure and mixtures thereof.

6. The method according to any one of claims 1 to 5, wherein the 1-dimensional structure and the one or more other dimensional structures are covalently or non-covalently bound.

7. The method of claim 6, wherein the 1-dimensional structure and the one or more other dimensional structures are combined to form a 3-dimensional network.

8. The method according to any one of claims 1 to 7, wherein the material is a carbon material comprising a polymer.

9. The method according to claim 8, wherein the mixture is formed by loading the polymer with the catalyst particles by surface wetting.

10. The method according to claim 8, wherein the mixture is formed by melt mixing a polymer supported with catalyst particles.

11. The method of any one of claims 1-10, wherein the material is a waste product comprising carbon.

12. The process according to any one of claims 1 to 11, wherein the catalyst is selected from iron chloride (II), nickel chloride (II), cobalt chloride (II) and ferrocene.

13. The method according to any one of claims 1 to 11, wherein the catalyst is selected from any transition metal or main group metal or transition metal or main group metal complex, salt, oxide, halide or combination thereof.

14. The method of any one of claims 1-13, wherein the mixture further comprises a conductive carbon additive.

15. The method of claim 14, wherein the conductive carbon additive is selected from the group consisting of graphene, flash graphene, turbostratic graphene, anthracite, coconut shell derived carbon, pyrotreated biochar, activated carbon, calcined petroleum coke, metallurgical coke, coke, shungite, carbon nanotubes, asphaltenes, acetylene black, carbon black, ash, carbon fibers, and mixtures thereof.

16. The method of claim 14, wherein the conductive carbon additive comprises carbon black and / or metallurgical coke.

17. The method of any one of claims 14 to 16, wherein the method further comprises, after the flash Joule heating, separating at least some of the conductive carbon additive from the formed 1-dimensional structure.

18. The method of claim 17, wherein the separating step is based on the particle size of the conductive carbon additive and the size of the formed 1-dimensional structure.

19. The method of claim 18, wherein the separating step comprises sieving to separate small 1-dimensional structures from large particle conductive carbon additives.

20. The method of claim 19, wherein after the separation step, the % yield of the 1-dimensional structures formed in the method is at least 80%.

21. The method of claim 19, wherein after the separation step, the % yield of the 1-dimensional structures formed in the method is between 80% and 90%.

22. The method of any one of claims 1-19, wherein the % yield of 1-dimensional structures formed in the method is at least 65%.

23. The method of any one of claims 1-19, wherein the % yield of the 1-dimensional structures formed in the method is at least 80%.

24. A 1-dimensional structure produced by the method of any one of claims 1-23.

25. The 1-dimensional structure according to claim 24, wherein the 1-dimensional structure is any form of nanostructure or microstructure, wherein the length of the 1-dimensional structure is at least 3 times the width of the 1-dimensional structure.

26. A 1-dimensional structure according to claim 24, wherein said 1-dimensional structure is not a single atom sheet thick.

27. A composite comprising the 1-dimensional structure of any one of claims 24-26.

28. The composite according to claim 27, wherein the composite comprises the 1-dimensional structure and a vinyl ester.

29. The composite according to claim 27, wherein the composite is a 1-dimensional structure-reinforced vinyl ester resin nanocomposite.

30. A structure or network prepared by the method of any one of claims 1-23.

31. A structure or network according to claim 30, wherein the 1-dimensional structure of the structure or network is any form of nanostructure or microstructure, wherein the length of the 1-dimensional structure is at least 3 times the width of the 1-dimensional structure.

32. A structure or network according to claim 30, wherein the 1-dimensional structure of the structure or network is not a single atom sheet thick.

33. A method comprising flash Joule heating a mixture to form boron nitride nanotubes, wherein the mixture comprises (i) a material comprising boron, (ii) a material comprising nitrogen, and (iii) a catalyst.

34. A method according to claim 33, wherein (a) the flash Joule heating is a process comprising applying a voltage across the mixture, which drives an electric current through the mixture to form the boron nitride nanotubes; (b) applying a voltage in the form of one or more voltage pulses; as well as (c) The duration of each of the one or more voltage pulses is a duration period.

35. The method of any one of claims 33 to 34, wherein the boron-containing material and the nitrogen-containing material are different materials.

36. The method of any one of claims 33 to 34, wherein the boron-containing material and the nitrogen-containing material are the same material.

37. The method of claim 36, wherein the same material is ammonia borane.

38. The method of any one of claims 33-37, wherein the catalyst is Ni(acac)2 and / or Fe(acac)3.

39. The method of any one of claims 33-37, wherein the catalyst comprises Ni and / or Fe.

40. A method according to any one of claims 33 to 39, wherein the mixture further comprises a conductive carbon source.

41. The method of claim 40, wherein the conductive carbon source is selected from the group consisting of graphene, flash graphene, turbostratic graphene, anthracite, coconut shell derived carbon, pyrotreated biochar, activated carbon, calcined petroleum coke, metallurgical coke, coke, shungite, carbon nanotubes, asphaltenes, acetylene black, carbon black, ash, carbon fibers, and mixtures thereof.

42. The method of claim 40, wherein the conductive carbon source comprises carbon black and / or metallurgical coke.

43. A method according to any one of claims 40 to 42, wherein the mixture comprises (i) a boron-containing material and a nitrogen-containing material and (b) a conductive carbon source in a weight ratio of 1:2 to 2:

1.

44. The method of any one of claims 40-43, wherein after the flash Joule heating, the method further comprises separating at least some of the conductive carbon source from the formed boron nitride nanotubes.

45. The method of claim 44, wherein the separating step is based on the particle size of the conductive carbon source and the size of the boron nitride nanotubes formed.

46. ​​The method of claim 45, wherein the separating step comprises screening to separate small boron nitride nanotubes from large particle conductive carbon sources.

47. The method of claim 46, wherein after the separation step, the yield % of boron nitride nanotubes formed in the method is at least 45%.

48. The method of claim 46, wherein after the separation step, the % yield of the 1-dimensional structure formed in the method is at least 60%.

49. The method of claims 40-46, wherein the % yield of the boron nitride nanotubes formed in the method is at least 45%.

50. The method of any one of claims 40-46, wherein the % yield of the boron nitride nanotubes formed in the method is at least 60%.

51. The method of any one of claims 40-50, wherein the product of the method comprises the boron nitride nanotubes and sheet-like structures.

52. The method of claim 51, wherein at least 30% of the product of the method is boron nitride nanotubes.

53. A composition comprising boron nitride nanotubes prepared by the method of any one of claims 33-52.

54. A method comprising flash Joule heating a mixture to form a turbostratic nanomaterial comprising (a) boron, (b) nitrogen, and (c) a third element selected from carbon, tungsten, or iron, wherein the mixture comprises (i) a material comprising boron, (ii) a material comprising nitrogen, and (iii) a material comprising the third element.

55. The method according to claim 54, wherein (a) The flash Joule heating is a process that involves applying a voltage across the mixture, which drives an electric current through the mixture to form a turbostratic nanomaterial; (b) applying a voltage in the form of one or more voltage pulses; and (c) The duration of each of the one or more voltage pulses is a duration period.

56. The method of any one of claims 54-55, wherein the third element is carbon and the turbostratic nanomaterial is turbostratic BCN.

57. The method of any one of claims 54-55, wherein the third element is tungsten and the turbostratic nanomaterial is turbostratic BN-W.

58. The method of any one of claims 54-55, wherein the third element is iron and the turbostratic nanomaterial is turbostratic BN-Fe.

59. A method according to any one of claims 54 to 58, wherein the mixture comprises (i) a material comprising boron and a material comprising nitrogen and (b) a material comprising a third element in a weight ratio higher than 4:

1.

60. The method according to any one of claims 54 to 58, wherein the mixture comprises (i) a material comprising boron and a material comprising nitrogen and (b) a material comprising a third element in a weight ratio of 1:2 to 2:

1.

61. The method of any one of claims 54-60, wherein the % yield of turbostratic nanomaterial formed in the method is at least 20%.

62. The method of any one of claims 54-60, wherein the % yield of turbostratic nanomaterial formed in the method is at least 30%.

63. A composition comprising a turbostratic nanomaterial comprising (a) boron, (b) nitrogen, and (c) a third element selected from carbon, tungsten, and iron, wherein the composition is prepared by any one of the methods of claims 54-62.

64. A method of forming doped or substituted graphene, wherein the method comprises: (a) performing a first flash Joule heating process using a first mixture to form a first formed graphene, wherein the first mixture comprises (i) a carbon source that is substantially not graphene and (ii) a catalyst; (b) mixing one or more heteroatom doping compounds with the first formed graphene to form a second mixture; and (c) performing a second flash Joule heating process using the second mixture to form the doped or substituted graphene.

65. A method according to claim 64, wherein (a) the first flash Joule heating process comprises applying a first voltage across the first mixture which drives a first current through the first mixture to form a first formed graphene; (b) applying a first voltage in the form of one or more first voltage pulses; (c) the duration of each of the one or more first voltage pulses is a first duration period; (d) the second flash Joule heating process includes applying a second voltage across the second mixture that drives a second current through the second mixture to form the doped or substituted graphene; (e) applying the second voltage in one or more second voltage pulses; as well as (f) The duration of each of the one or more second voltage pulses is a second duration period.

66. The method of any one of claims 64-66, wherein the first-formed graphene is a 1-dimensional structure.

67. The method of claim 66, wherein the 1-dimensional structure is formed by a method according to any one of claims 1 to 23.

68. The method of any one of claims 64-66, wherein the first formed graphene is a porous and wrinkled graphene.

69. The method of any one of claims 64-66, wherein the first-formed graphene is turbostratic graphene.

70. The method of any one of claims 64-69, wherein the carbon material comprises a polymer.

71. The method of any one of claims 64-69, wherein the carbon material is a waste product comprising carbon.

72. The method of any one of claims 64-69, wherein the carbon material is a plastic.

73. The method of any one of claims 64-69, wherein the carbon material is selected from graphene, flash graphene, turbostratic graphene, anthracite, coconut shell derived carbon, pyrotreated biochar, activated carbon, calcined petroleum coke, metallurgical coke, coke, shungite, carbon nanotubes, asphaltenes, acetylene black, carbon black, ash, carbon fibers, and mixtures thereof.

74. The method of any one of claims 64-69, wherein the conductive carbon material comprises metallurgical coke and / or asphaltene activated carbon.

75. The process of any one of claims 64 to 74, wherein the catalyst is selected from iron chloride (II), nickel chloride (II), cobalt chloride (II) and ferrocene.

76. The process according to any one of claims 64 to 74, wherein the catalyst is selected from any transition metal or main group metal or a complex, salt, oxide, halide or combination thereof of a transition metal or main group metal.

77. The method of any one of claims 64 to 76, wherein the method further comprises separating at least some of the carbon material from the formed first formed graphene after the first flash Joule heating process.

78. The method of claim 77, wherein the separating step is based on a particle size of the carbon material and a size of the first formed graphene.

79. The method of claim 77, wherein the separating step comprises sieving to separate the small first-formed graphenes from large particulate carbon material.

80. The method of any one of claims 64-78, wherein the step of mixing to form the second mixture comprises mixing exactly one heteroatom doping compound with the first-formed graphene.

81. The method of any one of claims 64-78, wherein the step of mixing to form the second mixture comprises mixing two or more heteroatom doping compounds with the first formed graphene.

82. The method of any one of claims 64 to 80, wherein the one or more heteroatom dopant compounds each comprise at least one heteroatom selected from the group consisting of boron, nitrogen, sulfur, and fluorine.

83. The method according to any one of claims 64-80, wherein the one or more heteroatom doping compounds are each selected from boric acid, melamine resin, polyphenylene sulfide, and perfluorooctanoic acid.

84. The method of any one of claims 64-80, wherein the one or more heteroatom doping compounds comprise an organic powder having a low melting point.

85. The method of any one of claims 64 to 83, wherein the ratio of (i) the one or more heteroatom doping compounds to (ii) the first-formed graphene is between 1:8 and 1:2 by weight.

86. The method of any one of claims 64 to 85, wherein the second flash Joule heating process is performed under an argon atmosphere.

87. The method of any one of claims 64-86, wherein the carbon source has a large particle size.

88. A method according to any one of claims 64 to 86, wherein (a) performing a second flash Joule heating process using a first second flash Joule heating voltage and a second flash Joule heating voltage; and (b) The second flash Joule heating voltage is greater than the first flash Joule heating voltage.

89. The method of claim 88, wherein the second second flash Joule heating voltage is at least twice the first second flash Joule heating voltage.

90. The method of claim 88, wherein the second second flash Joule heating voltage is at least five times greater than the first second flash Joule heating voltage.

91. The method of any one of claims 64 to 90, wherein the second flash Joule heating process is performed using pulse width modulated DC electrical pulses discharged from a capacitor bank.

92. The method of any one of claims 64 to 90, wherein the second flash Joule heating process is performed using modulated or non-modulated AC and DC current sources.

93. A method according to any one of claims 64 to 92, wherein (a) performing the first flash Joule heating process in a first cylindrical reactor having a first diameter; (b) performing the second flash Joule heating process in a second cylindrical reactor having a second diameter; and (c) The first diameter is larger than the second reactor.

94. The method of any one of claims 64 to 93, wherein the doped or substituted graphene comprises heteroatoms doped into the graphene lattice.

95. The method of any one of claims 64 to 93, wherein the doped or substituted graphene comprises heteroatoms above or below the graphene lattice.

96. The method of any one of claims 64 to 93, wherein the doped or substituted graphene comprises heteroatoms doped into the graphene lattice and heteroatoms above or below the graphene lattice.

97. The method of any one of claims 64-96, wherein the doping rate of the doped or substituted graphene is at least 10%.

98. The method of any one of claims 64-96, wherein the doping rate of the doped or substituted graphene is at least 20%.

99. Doped or substituted graphene prepared by any one of the methods of claims 64-98.

100. A method comprising mixing the doped or substituted graphene of claim 99 in concrete to increase the mechanical strength of the concrete.

101. A concrete comprising the doped or substituted graphene according to claim 99.

102. A method comprising mixing the doped or substituted graphene of claim 99 into an epoxy resin to increase the mechanical strength of the epoxy resin.

103. An epoxy resin comprising the doped or substituted graphene of claim 99.

104. A battery having a battery electrode comprising the doped or substituted graphene of claim 99.

Citation Information

Patent Citations

  • Fungicide mixture and method for controlling harmful fungi

    EA004958B1

  • Flash joule heating synthesis method and compositions thereof

    US20210206642A1

  • Ultrafast flash joule heating synthesis methods and systems for performing same

    WO2022067111A2